Polycarbonate resin film

By using specific dihydroxy compounds and high-performance ultraviolet absorbers in the polycarbonate resin film, the heat resistance and appearance problems of the polycarbonate resin film in the protection of polarizers are solved, and the preparation of high-performance optical film is realized.

CN119119705APending Publication Date: 2024-12-13MITSUBISHI CHEM CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411187827.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2015-04-21
Filing Date
2016-04-20
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the protection of polarizers, the existing polycarbonate resin film lacks ultraviolet absorption ability, which leads to reduced heat resistance, turbidity caused by exudate, foreign matter and gear patterns caused by roller contamination, and has uneven thickness.

Method used

A polycarbonate resin containing specific dihydroxy compound structural units is used to combine ultraviolet absorbers with high melting point and high weight loss temperature to control the terminal group structure and compound content of the polycarbonate resin to form a thin film with excellent ultraviolet absorption properties.

Benefits of technology

A high-performance optical film is realized, reducing appearance defective products, improving productivity and product quality, ensuring the uniform thickness and heat resistance of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119705A_ABST
    Figure CN119119705A_ABST
Patent Text Reader

Abstract

The invention relates to a polycarbonate resin film. The present invention addresses the problem of providing, from a polycarbonate resin containing a specific polycarbonate resin and a specific ultraviolet light absorber, a film that absorbs specific ultraviolet light without roll contamination or bleeding. The present invention relates to a polycarbonate resin film which is formed from a polycarbonate resin composition containing: 100 parts by weight of a polycarbonate resin containing a structural unit derived from a dihydroxy compound represented by formula (1); and more than 0.45 parts by weight but not more than 7 parts by weight of an ultraviolet absorber having a melting point of 135 DEG C to less than 300 DEG C and a 5% weight loss temperature of greater than 240 DEG C per 100 parts by weight of a polycarbonate resin, said polycarbonate resin film having a light transmittance of 0.001% to 15% at a wavelength of 380 nm and a thickness of 5 [mu] m to 120 [mu] m # imgabs 0 #
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present application is a divisional application of an application filed on April 20, 2016, with application number 201680023251.9 and invention name “Polycarbonate Resin Film”. Technical Field

[0002] The present invention relates to a polycarbonate resin film formed from a polycarbonate resin composition, a polarizer protective film using the same, and a polycarbonate resin composition. Background Art

[0003] Conventionally, as a method for obtaining a polycarbonate resin, the following method has been proposed: using isosorbide (hereinafter sometimes referred to as ISB), a dihydroxy compound obtained from biomass resources, as a monomer component, and performing ester exchange with a carbonic acid diester, while distilling off the by-produced monohydroxy compound under reduced pressure, to obtain a polycarbonate resin (see, for example, Patent Documents 1 to 4). In addition to being used as a molding material that exhibits heat resistance, the polycarbonate resin obtained from ISB has also been studied for its use in optical films that exhibit excellent optical properties (see, for example, Patent Document 5).

[0004] In order to protect the polarizer from ultraviolet rays, a UV absorber is added to a general polarizer protective film. However, the amount of the UV absorber must be large, and there are problems such as bleeding. In order to eliminate these problems, there is a known method of adding a UV absorber with high compatibility with the resin or a polymer having a UV absorbing function (for example, see Patent Document 6).

[0005] However, generally speaking, the cellulose ester film used in the polarizer protective film has high water absorption, and has a problem of insufficient durability when used in large-scale televisions, etc. In addition, a polarizer protective film using acrylic resin has also been proposed (for example, see Patent Document 7), but due to its brittleness, it sometimes breaks during handling and is difficult to form into a film.

[0006] In addition, in the case of a display using a general polarizing plate, the light across the polarizing plate is linearly polarized light, so when the display is viewed through polarized sunglasses, black vision sometimes occurs due to the angle. In order to eliminate this, the surface layer of the polarizer protective film is sometimes made into a phase difference film (for example, refer to Patent Document 8). These phase difference films also contain ultraviolet absorbers to protect the polarizer from ultraviolet rays.

[0007] For example, when using cycloolefin polymer (hereinafter sometimes abbreviated as COP), there is a technique of forming two types of three layers and containing a UV absorber only in the core layer in order to prevent bleeding and roll contamination (see, for example, Patent Document 9).

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: International Publication No. 2004 / 111106

[0011] Patent Document 2: Japanese Patent Application Publication No. 2006-232897

[0012] Patent Document 3: Japanese Patent Application Publication No. 2006-28441

[0013] Patent Document 4: Japanese Patent Application Publication No. 2008-24919

[0014] Patent Document 5: Japanese Patent Application Publication No. 2011-021171

[0015] Patent Document 6: Japanese Patent Application Publication No. 2002-047357

[0016] Patent Document 7: Japanese Patent Application Publication No. 2013-83956

[0017] Patent Document 8: Japanese Patent Application Publication No. 2011-137954

[0018] Patent Document 9: Japanese Patent Application Publication No. 2015-31753 Summary of the invention

[0019] Problem that the invention aims to solve

[0020] However, the polycarbonate resin obtained from ISB has almost no ultraviolet absorption, so when used for polarizer protective films, it must contain a large amount of ultraviolet absorbers. On the other hand, when the polycarbonate resin contains a large amount of ultraviolet absorbers, there are problems such as reduced heat resistance of the film, turbidity of the film caused by exuded substances, foreign matter in the film due to roller contamination, poor appearance of the film such as gear marks, and reduced uniformity of film thickness. In addition, roller contamination may occur due to specific compounds.

[0021] Therefore, the object of the present invention is to eliminate these problems and use a specific polycarbonate resin containing a specific ultraviolet absorber to provide: a polycarbonate resin film having a uniform film thickness and absorbing specific ultraviolet rays without problems such as reduced heat resistance of the film, turbidity of the film caused by oozing substances, foreign matter in the film due to roller contamination, and poor appearance of the film such as gear marks.

[0022] Solutions for solving problems

[0023] The present inventors have conducted intensive studies to solve the above problems and have found that by using a polycarbonate resin containing a structural unit derived from a dihydroxy compound represented by the following formula (1) and adding a specific ultraviolet absorber, a high-quality film that absorbs specific ultraviolet rays can be provided without problems such as reduced heat resistance of the film, turbidity of the film due to oozing substances, foreign matter in the film due to roll contamination, and poor appearance of the film such as cogwheel marks, and the like, thereby completing the present invention. That is, the gist of the present invention is the following [1] to [6].

[0024] [1] A polycarbonate resin film, which is a polycarbonate resin film formed from a polycarbonate resin composition, the polycarbonate resin composition comprising: 100 parts by weight of a polycarbonate resin containing a structural unit derived from a dihydroxy compound represented by the following formula (1); and more than 0.45 parts by weight and less than 7 parts by weight of an ultraviolet absorber having a melting point of 135°C to less than 300°C and a 5% weight loss temperature of more than 240°C, based on 100 parts by weight of the polycarbonate resin, wherein the polycarbonate resin film has a light transmittance of 0.001% to 15% at a wavelength of 380 nm and a thickness of 5 μm to 120 μm.

[0025]

[0026] [2] The polycarbonate resin film according to [1], wherein the content of the compound represented by the following formula (3) in the polycarbonate resin is 10 ppm by weight or more and 1200 ppm by weight or less.

[0027]

[0028] [3] The polycarbonate resin film according to [1] or [2], wherein the ultraviolet absorber is a triazine-based, benzotriazole-based, quinolinone-based, benzoxazole-based, or indole-based ultraviolet absorber.

[0029] [4] The polycarbonate resin film according to any one of [1] to [3], wherein the in-plane retardation at 548 nm is 100 nm to 200 nm.

[0030] [5] A polarizer protective film comprising the polycarbonate resin film according to any one of [1] to [4].

[0031] [6] A polycarbonate resin composition comprising: 100 parts by weight of a polycarbonate resin comprising a structural unit derived from a dihydroxy compound represented by the following formula (1); and an ultraviolet absorber having a melting point of 135°C to less than 300°C and a 5% weight loss temperature of more than 0.45 parts by weight and less than 7 parts by weight, based on 100 parts by weight of the polycarbonate resin, wherein the content of the compound represented by the following formula (3) in the polycarbonate resin is 10 ppm by weight to 1200 ppm by weight.

[0032]

[0033] Effects of the Invention

[0034] According to the present invention, although a large amount of ultraviolet absorber is contained, when the film is formed into a film, there will be no problems such as reduced heat resistance of the film, turbidity of the film due to exuded substances, foreign matter in the film due to roller contamination, poor appearance of the film such as gear marks, etc., and the optical film showing high performance as a polarizer protective film can be provided. Furthermore, since roller contamination is not generated, it is possible to significantly reduce the number of defective appearance products during molding, thereby improving productivity, workability, and product quality. DETAILED DESCRIPTION

[0035] Hereinafter, an embodiment of the present invention will be described in detail. However, the description of the features described below is an example (representative example) of the embodiment of the present invention, and the present invention is not limited to the following contents unless exceeding the gist thereof.

[0036] The polycarbonate resin film of the present invention is formed from a polycarbonate resin composition containing a polycarbonate resin and an ultraviolet absorber.

[0037] [Polycarbonate resin]

[0038] The polycarbonate resin composition in the present invention contains a polycarbonate resin including a structural unit derived from a dihydroxy compound represented by the following formula (1).

[0039]

[0040] (Terminal group structure of polycarbonate resin)

[0041] The polycarbonate resin can be produced by polycondensing a dihydroxy compound, a carbonic acid diester and a catalyst under melting. As the carbonic acid diester, the carbonic acid diester described below can be used. Among them, diphenyl carbonate is preferably used.

[0042] At this time, the ratio (A / B) of the number of terminal groups (A) represented by the following structural formula (2) (hereinafter sometimes referred to as "phenyl terminals") in the produced polycarbonate resin relative to the total number of terminals (B) is preferably in the range of 75% or more and less than 98%.

[0043]

[0044] The ratio (A / B) of the number of phenyl terminals (A) in the polycarbonate resin to the total number of terminals (B) is more preferably 76% or more, particularly preferably 77% or more, and more preferably 96% or less, particularly preferably 95% or less.

[0045] When the ratio (A / B) of the number of phenyl terminals (A) to the total number of terminals (B) is less than 75%, poor appearance called silver streaks are likely to occur in the molded product during injection molding, and bubbles are likely to occur during extrusion molding. In addition, when the ratio (A / B) of the number of phenyl terminals (A) to the total number of terminals (B) is greater than 98%, there is a tendency to reduce poor appearance during injection molding and extrusion molding. In addition, when it is desired to obtain a polycarbonate resin having a ratio (A / B) greater than 98%, the polymerization conditions are made strict or a long reaction time is required, resulting in the deterioration of the polycarbonate resin, and there is a high possibility that only a product with a poor color tone can be obtained.

[0046] The method for adjusting the ratio (A / B) of the number of phenyl terminals (A) of the polycarbonate resin to the total number of terminals (B) to the above range is not particularly limited. For example, the ratio of the carbonic acid diester amount to the total dihydroxy compound used in the reaction is adjusted to a range that can obtain a desired high molecular weight body, or the residual monomer is removed to the outside of the reaction system by degassing in the latter stage of the polymerization reaction, or the stirring efficiency of the reactor in the latter stage of the polymerization reaction is increased to increase the reaction rate, thereby adjusting the ratio (A / B) of the number of phenyl terminals (A) to the total number of terminals (B) to the above range.

[0047] The ratio of the phenyl terminal in the polycarbonate resin can be determined by NMR spectrometry using deuterated chloroform to which TMS (tetramethylsilane) is added as a measurement solvent. 1 It was calculated by measuring the H-NMR spectrum.

[0048] The ratio of the dihydroxy compound having the bond structure of the structural formula (1), the alicyclic dihydroxy compound, and other dihydroxy compounds used as required is appropriately adjusted according to the ratio of the structural units derived from the dihydroxy compounds constituting the polycarbonate resin used in the present invention.

[0049] (Content of the compound represented by formula (3) and method for controlling the content)

[0050] The polycarbonate resin in the present invention more preferably contains a specific amount of a special oligomer component represented by the following formula (3).

[0051]

[0052] When the amount of the above-mentioned compound is too small, in the manufacturing stage of the polycarbonate resin, excess heat is sometimes consumed, or the reaction residence time becomes long, which may cause the color tone of the polymer to deteriorate. In addition, when it is too much, the problem of device contamination during molding or the problem of poor appearance of the molded product may occur. Therefore, the content of the compound represented by formula (3) in the polycarbonate resin of the present invention is preferably 10 ppm by weight or more and 1200 ppm by weight or less.

[0053] In addition, the content of the compound represented by formula (3) in the polycarbonate resin of the present invention is more preferably 15 ppm by weight or more, particularly preferably 20 ppm by weight or more. In addition, it is more preferably 650 ppm by weight or less, particularly preferably 400 ppm by weight or less. If the content of the compound represented by formula (3) in the polycarbonate resin is within the above range, contamination and odor during molding disappear, and the molding appearance is good, so it is preferred.

[0054] In order to adjust the content of the compound represented by formula (3), it is preferred that the ratio (A / B) of the number of phenyl terminals (A) to the total number of terminals (B) be 98% or less in the production of the polycarbonate resin.

[0055] Furthermore, by setting the pressure in the final polymerization tank to 1 kPa or less, or by setting the polymerization time at a temperature higher than 220° C. to less than 2 hours, the generation of the compound represented by formula (3) can be suppressed. In particular, by making the final polymerization tank a horizontal reaction tank, the devolatilization efficiency can be greatly improved. In addition, by performing devolatilization using a vacuum exhaust port in an extruder, or by injecting water during devolatilization, the compound represented by formula (3) can be controlled to a specific amount.

[0056] The polycarbonate resin in the present invention is generally obtained by polycondensing a dihydroxy compound, a carbonic acid diester and a catalyst under melt conditions as described below. In the polycondensation reaction, a monohydroxy compound is generated as a component removed from the carbonic acid diester.

[0057] For example, when diphenyl carbonate is used as the carbonic acid diester, the generated monohydroxy compound is phenol. In this case, the content of the monohydroxy compound in the obtained polycarbonate resin is high, and problems such as equipment contamination and odor during molding may occur.

[0058] The upper limit of the content of the monohydroxy compound in the polycarbonate resin of the present invention is not particularly limited, but is generally 1200 ppm by weight or less, preferably 650 ppm by weight or less, and particularly preferably 500 ppm by weight or less. When the polycarbonate resin is produced, an appropriate amount of a specific phosphorus compound that becomes a catalyst deactivator described later is used, and a devolatilization treatment is further performed sufficiently, thereby reducing the content of the monohydroxy compound in the polycarbonate resin and suppressing the generation under heating. The details of the method for determining the amount of the monohydroxy compound in the polycarbonate resin are described in the Examples.

[0059] In addition, as the lower limit, there is no particular restriction, but it is usually 0.1 wtppm or more, more preferably 1 wtppm or more, and particularly preferably 10 wtppm or more. When they are too small, excessive heat must be applied in the purification stage, or the reaction residence time must be extended, which may cause the color tone of the polymer to deteriorate, and the above range is preferred.

[0060] [Method for producing polycarbonate resin]

[0061] Hereinafter, the method for producing the polycarbonate resin in the present invention will be described in detail.

[0062] <Raw materials>

[0063] (Dihydroxy Compound)

[0064] The polycarbonate resin in the present invention is a polycarbonate resin containing a structural unit derived from a dihydroxy compound represented by the following formula (1).

[0065]

[0066] In the present invention, the polycarbonate resin preferably contains, in addition to the structural unit derived from the dihydroxy compound represented by the above formula (1), structural units derived from one or more dihydroxy compounds selected from the group consisting of a dihydroxy compound represented by the following formula (4), a dihydroxy compound represented by the following formula (5), a dihydroxy compound represented by the following formula (6), a dihydroxy compound represented by the following formula (7) and a dihydroxy compound represented by the following formula (8).

[0067]

[0068] HO-R 5 -OH(5)

[0069] (In the above formula (5), R 5 represents a substituted or unsubstituted cycloalkylene group having 4 to 20 carbon atoms.

[0070] HO-CH2-R 6 -CH2-OH(6)

[0071] (In the above formula (6), R 6 represents a substituted or unsubstituted cycloalkylene group having 4 to 20 carbon atoms.

[0072] H-(OR 7 ) p -OH(7)

[0073] (In the above formula (7), R 7 represents a substituted or unsubstituted alkylene group having 2 to 10 carbon atoms, and p is an integer of 2 to 100.

[0074] HO-R 8 -OH(8)

[0075] (In the above formula (8), R 8 represents a substituted or unsubstituted alkylene group having 2 to 20 carbon atoms. )

[0076] In addition, in the following, when the group has a substituent, the carbon number of various groups means the total carbon number including the carbon number of the substituent.

[0077] (Dihydroxy compound represented by formula (1))

[0078] The polycarbonate resin in the present invention contains a structural unit derived from the dihydroxy compound represented by the above formula (1).

[0079] As the dihydroxy compound represented by the above formula (1), for example, anhydrous sugar alcohols such as isosorbide, isomannide, and isoidide, which are in a stereoisomer relationship, can be cited. One of them can be used alone, or two or more of them can be used in combination. Among these dihydroxy compounds, the most preferred is isosorbide obtained by dehydration condensation of sorbitol, which is abundant in resources and produced from various starches that can be easily obtained, from the aspects of ease of acquisition and manufacture, optical properties, and formability.

[0080] When the polycarbonate resin contains structural units other than the structural unit derived from the dihydroxy compound represented by the above formula (1), the ratio thereof is not particularly limited and can be appropriately set according to the required performance of the polycarbonate resin.

[0081] (Dihydroxy compounds represented by formulas (4) to (8))

[0082] In the present invention, the polycarbonate resin may contain, as necessary, structural units derived from one or more dihydroxy compounds selected from the group consisting of the dihydroxy compound represented by the above formula (4), the dihydroxy compound represented by the above formula (5), the dihydroxy compound represented by the above formula (6), the dihydroxy compound represented by the above formula (7) and the dihydroxy compound represented by the above formula (8).

[0083] [Dihydroxy compound represented by formula (4)]

[0084] The dihydroxy compound represented by the above formula (4) is a compound which has a cyclic ether structure in the molecule and is called a spirodiol.

[0085] [Dihydroxy compound represented by formula (5)]

[0086] The dihydroxy compound represented by the above formula (5) is R 5 An alicyclic dihydroxy compound having a substituted or unsubstituted cycloalkylene group having 4 to 20 carbon atoms, preferably 4 to 18 carbon atoms. 5 When the group has a substituent, examples of the substituent include substituted or unsubstituted alkyl groups having 1 to 12 carbon atoms. When the group has a substituent, examples of the substituent include alkoxy groups such as methoxy, ethoxy, and propoxy, and aryl groups such as phenyl and naphthyl.

[0087] The dihydroxy compound has a ring structure, so that the toughness of a molded product when the obtained polycarbonate resin is molded can be improved, and in particular, the toughness when molded into a film can be improved.

[0088] As R 5 The cycloalkylene group is not particularly limited as long as it is a hydrocarbon group having a ring structure, and may be a bridged structure such as a bridgehead carbon atom. From the viewpoint that the dihydroxy compound is easy to manufacture and the amount of impurities can be reduced, the dihydroxy compound represented by the above formula (5) is preferably a compound containing a five-membered ring structure or a six-membered ring structure, that is, preferably R 5 A dihydroxy compound of a substituted or unsubstituted cyclopentylene group or a substituted or unsubstituted cyclohexylene group. If such a dihydroxy compound is used, the heat resistance of the obtained polycarbonate resin can be improved by including a five-membered ring structure or a six-membered ring structure. The six-membered ring structure can be fixed in a chair shape or a boat shape by a covalent bond.

[0089] Among them, the dihydroxy compound represented by the above formula (5) is preferably R 5 are various isomers represented by the following formula (9). Here, in formula (9), R 11 represents a hydrogen atom, or a substituted or unsubstituted alkyl group having 1 to 12 carbon atoms. 11In the case of an alkyl group having 1 to 12 carbon atoms and having a substituent, examples of the substituent include alkoxy groups such as methoxy, ethoxy, and propoxy, and aryl groups such as phenyl and naphthyl.

[0090]

[0091] More specifically, examples of the dihydroxy compound represented by the above formula (5) include tetramethylcyclobutanediol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, 1,2-cyclopentanediol, 1,3-cyclopentanediol, 1,2-cyclohexanediol, 1,3-cyclohexanediol, 1,4-cyclohexanediol, 2-methyl-1,4-cyclohexanediol, tricyclodecanediols, pentacyclic glycols, and the like, but the present invention is not limited to these.

[0092] These may be used alone or in combination of two or more.

[0093] [Dihydroxy compound represented by formula (6)]

[0094] The dihydroxy compound represented by the above formula (6) is R 6 An alicyclic dihydroxy compound having a substituted or unsubstituted cycloalkylene group having 4 to 20 carbon atoms, preferably 3 to 18 carbon atoms. 6 When the group has a substituent, examples of the substituent include substituted or unsubstituted alkyl groups having 1 to 12 carbon atoms. When the group has a substituent, examples of the substituent include alkoxy groups such as methoxy, ethoxy, and propoxy, and aryl groups such as phenyl and naphthyl.

[0095] The dihydroxy compound has a ring structure, so that the toughness of a molded product when the obtained polycarbonate resin is molded can be improved, and in particular, the toughness when molded into a film can be improved.

[0096] As R 6 The cycloalkylene group is not particularly limited as long as it is a hydrocarbon group having a ring structure, and may be a bridged structure such as a bridgehead carbon atom. From the viewpoint that the dihydroxy compound is easy to manufacture and the amount of impurities can be reduced, the dihydroxy compound represented by the above formula (6) is preferably a compound containing a five-membered ring structure or a six-membered ring structure, that is, preferably R 6 A dihydroxy compound which is a substituted or unsubstituted cyclopentylene group or a substituted or unsubstituted cyclohexylene group.

[0097] If such a dihydroxy compound is used, the heat resistance of the obtained polycarbonate resin can be improved by including a five-membered ring structure or a six-membered ring structure. The six-membered ring structure can be fixed in a chair shape or a boat shape by a covalent bond. In the dihydroxy compound represented by the above formula (6), R 6 Various isomers represented by the above formula (9) are preferred.

[0098] More specifically, the dihydroxy compound represented by the formula (6) includes 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, 3,8-bis(hydroxymethyl)tricyclo[5.2.1.0 2.6 ]decane, 3,9-bis(hydroxymethyl)tricyclo[5.2.1.0 2.6 ]decane, 4,8-bis(hydroxymethyl)tricyclo[5.2.1.0 2.6 ]decane, 4,9-bis(hydroxymethyl)tricyclo[5.2.1.0 2.6 ] decane, etc., but are not limited to these.

[0099] These may be used alone or in combination of two or more. That is, these dihydroxy compounds may be obtained as a mixture of isomers for production reasons, and in this case, they may be used as is in the form of the isomer mixture.

[0100] For example, 3,8-bis(hydroxymethyl)tricyclo[5.2.1.0 2.6 ]decane, 3,9-bis(hydroxymethyl)tricyclo[5.2.1.0 2.6 ]decane, 4,8-bis(hydroxymethyl)tricyclo[5.2.1.0 2.6 ]decane and 4,9-bis(hydroxymethyl)tricyclo[5.2.1.0 2.6 ]A mixture of decane, etc.

[0101] Among the specific examples of the dihydroxy compound represented by the above formula (6), cyclohexanedimethanols are particularly preferred, and 1,4-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, and 1,2-cyclohexanedimethanol are preferred from the viewpoint of availability and ease of handling.

[0102] [Dihydroxy compound represented by formula (7)]

[0103] The dihydroxy compound represented by the above formula (7) is R 7 The compound has a substituted or unsubstituted alkylene group having 2 to 10 carbon atoms, preferably 2 to 5 carbon atoms. p is an integer of 2 to 100, preferably an integer of 6 to 50, and more preferably an integer of 12 to 40.

[0104] Specific examples of the dihydroxy compound represented by the above formula (7) include diethylene glycol, triethylene glycol, polyethylene glycol (molecular weight 150 to 4000), etc., but the present invention is not limited to these. As the dihydroxy compound represented by the above formula (7), polyethylene glycol with a molecular weight of 300 to 2000 is preferred, and polyethylene glycol with a molecular weight of 600 to 1500 is particularly preferred.

[0105] These may be used alone or in combination of two or more.

[0106] [Dihydroxy compound represented by formula (8)]

[0107] In the dihydroxy compound represented by the above formula (8), R 8 It is a substituted or unsubstituted alkylene group having 2 to 20 carbon atoms, preferably 2 to 10 carbon atoms. 8 When the alkylene group has a substituent, examples of the substituent include an alkyl group having 1 to 5 carbon atoms.

[0108] In the dihydroxy compound represented by the above formula (8), R 8 Specific examples of the dihydroxy compound which is a substituted or unsubstituted alkylene group having 2 to 20 carbon atoms include ethylene glycol, propylene glycol, 1,4-butanediol, and 1,6-hexanediol, but the present invention is not limited to these.

[0109] Among these dihydroxy compounds, 1,3-propylene glycol and 1,6-hexanediol are preferred from the viewpoints of ease of acquisition, ease of handling, high reactivity during polymerization, and the hue of the obtained polycarbonate resin. Furthermore, from the viewpoint of heat resistance, spirocyclic diols having an acetal ring are preferred. These can be used alone or in combination of two or more depending on the required performance of the obtained polycarbonate resin.

[0110] It should be noted that in the present invention, for the polycarbonate resin, among the structural units derived from the dihydroxy compound represented by the above formula (4), the structural units derived from the dihydroxy compound represented by the above formula (5), the structural units derived from the dihydroxy compound represented by the above formula (6), the structural units derived from the dihydroxy compound represented by the above formula (7), and the structural units derived from the dihydroxy compound represented by the above formula (8), it is preferred to include: the structural units derived from the dihydroxy compound represented by the above formula (6) and / or the structural units derived from the dihydroxy compound represented by the above formula (7). In addition, from the aspects of reactivity, heat resistance, and less decomposition during heat retention, it is more preferred to include the structural units derived from the dihydroxy compound represented by the above formula (6).

[0111] (Other dihydroxy compounds)

[0112] In the present invention, in the polycarbonate resin, the structural unit derived from the dihydroxy compound represented by the above formulae (4) to (8) may be replaced with a structural unit derived from another dihydroxy compound as necessary.

[0113] Examples of other dihydroxy compounds include bisphenols, ethylene oxide (EO) addition compounds of bisphenols, and fluorene compounds.

[0114] <Bisphenols>

[0115] Examples of the bisphenols include 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 2,2-bis(4-hydroxy-3,5-diethylphenyl)propane, 2,2-bis(4-hydroxy-(3,5-diphenyl)phenyl)propane, 2,2-bis(4-hydroxy-3,5-dibromophenyl)propane, 2,2-bis(4-hydroxyphenyl)pentane, 2,4'-dihydroxy-diphenylmethane, ... 1,1-bis(4-hydroxyphenyl)ethane, 3,3-bis(4-hydroxyphenyl)pentane, 1,1-bis(4-hydroxyphenyl)cyclohexane, bis(4-hydroxyphenyl)sulfone, 2,4'-dihydroxydiphenylsulfone, bis(4-hydroxyphenyl)sulfide, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dichlorodiphenyl ether, 4,4'-dihydroxy-2,5-diethoxydiphenyl ether, etc.

[0116] <Ethylene oxide (EO) addition of bisphenols>

[0117] Examples of ethylene oxide (EO)-added bisphenols include those obtained by adding ethylene oxide (EO) to the above-mentioned bisphenol compounds.

[0118] <Fluorene compounds>

[0119] Examples of the fluorene compound include 9,9-bis(4-hydroxyphenyl)fluorene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 9,9-bis(4-hydroxy-3-ethylphenyl)fluorene, 9,9-bis(4-hydroxy-3-n-propylphenyl)fluorene, 9,9-bis(4-hydroxy-3-isopropylphenyl)fluorene, 9,9-bis(4-hydroxy-3-n-butylphenyl)fluorene, 9,9-bis(4-hydroxy-3-sec-butylphenyl)fluorene, 9,9-bis(4-hydroxy-3-tert-propylphenyl)fluorene, 9,9-bis(4-hydroxy-3-cyclohexylphenyl)fluorene, 9,9-bis(4-hydroxy-3-phenylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)phenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)phenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-methylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-isopropylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-isobutylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-tert-butylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-cyclohexylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-phenylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3,5-dimethylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-tert-butyl-6-methylphenyl)fluorene, 9,9-bis(4-(3-hydroxy-2,2-dimethylpropyloxy)phenyl)fluorene, etc.

[0120] They can be used alone or in combination of two or more. However, dihydroxy compounds having an aromatic ring in their structure other than the substance represented by the above formula (1) may have adverse effects on optical properties. Therefore, the structural units derived from such dihydroxy compounds are preferably used at 50 mol% or less, more preferably 20 mol% or less, and further preferably 5 mol% or less relative to the total of the structural units derived from the dihydroxy compounds in the polycarbonate resin. It is particularly preferred that the polycarbonate resin does not contain structural units derived from dihydroxy compounds having an aromatic ring in their structure other than the substance represented by the above formula (1).

[0121] [Content ratio of structural units derived from dihydroxy compounds]

[0122] In the present invention, the content ratio of the structural unit derived from the dihydroxy compound represented by the above formula (1) contained in the polycarbonate resin is preferably 20% by weight or more, more preferably 25% by weight or more, and further preferably 30% by weight or more, relative to the total amount of the structural unit derived from the dihydroxy compound. In addition, it is usually 95% by weight or less, preferably 90% by weight or less.

[0123] When the content ratio of the structural unit is too low, the heat resistance is low and the surface hardness may be poor. In addition, when the content ratio of the structural unit is too high, the glass transition temperature of the polycarbonate resin may be too high to be difficult to form, or the water absorption rate may be deteriorated.

[0124] In addition, when the polycarbonate resin contains structural units derived from one or more dihydroxy compounds selected from the group consisting of the dihydroxy compound represented by the above formula (4), the dihydroxy compound represented by the above formula (5), the dihydroxy compound represented by the above formula (6), the dihydroxy compound represented by the above formula (7) and the dihydroxy compound represented by the above formula (8), the content ratio thereof is preferably 0.1% by weight or more and less than 20% by weight, more preferably 0.1% by weight or more and less than 18% by weight, and further preferably 0.2% by weight or more and less than 15% by weight, relative to the total amount of structural units derived from the dihydroxy compounds contained in the polycarbonate resin.

[0125] By including the structural units derived from dihydroxy compounds represented by the above formulae (4) to (8) in a polycarbonate resin in an amount greater than the above lower limit, the generation of foreign matter and bubbles due to heat can be prevented when the polycarbonate resin is melted and molded, and the coloring of the polycarbonate resin can be prevented. However, when the structural units are excessively high, the light resistance of the molded article tends to decrease.

[0126] All dihydroxy compounds used in the manufacture of the polycarbonate resin in the present invention may contain stabilizers such as reducing agents, antioxidants, deoxidizers, light stabilizers, antacids, pH stabilizers or heat stabilizers. The specific dihydroxy compounds in the present invention are easily deteriorated in acidic conditions, and therefore, it is particularly preferred to contain a basic stabilizer.

[0127] Examples of the alkaline stabilizer include hydroxides, carbonates, phosphates, phosphites, hypophosphites, borates and fatty acid salts of metals of Group 1 or Group 2 in the long-period periodic table (Nomenclature of Inorganic Chemistry IUPAC Recommendations 2005), alkaline ammonium hydroxides such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, trimethylethylammonium hydroxide, trimethylbenzylammonium hydroxide, trimethylphenylammonium hydroxide, triethylmethylammonium hydroxide, triethylbenzylammonium hydroxide, triethylphenylammonium hydroxide, tributylbenzylammonium hydroxide, tributylphenylammonium hydroxide, tetraphenylammonium hydroxide, benzyltriphenylammonium hydroxide, methyltriphenylammonium hydroxide and butyltriphenylammonium hydroxide. Amine compounds such as compounds, diethylamine, dibutylamine, triethylamine, morpholine, N-methylmorpholine, pyrrolidine, piperidine, 3-amino-1-propanol, ethylenediamine, N-methyldiethanolamine, diethylethanolamine, 4-aminopyridine, 2-aminopyridine, N,N-dimethyl-4-aminopyridine, 4-diethylaminopyridine, 2-hydroxypyridine, 2-methoxypyridine, 4-methoxypyridine, 2-dimethylaminoimidazole, 2-methoxyimidazole, imidazole, 2-mercaptoimidazole, 2-methylimidazole and aminoquinoline, and hindered amine compounds such as di-(tert-butyl)amine and 2,2,6,6-tetramethylpiperidine. Among these stabilizers, tetramethylammonium hydroxide, imidazole or hindered amine compounds are preferred from the perspective of stabilization effect.

[0128] The content of these alkaline stabilizers in the total dihydroxy compounds used in the present invention is not particularly limited. The aforementioned specific dihydroxy compounds used in the present invention are unstable in an acidic state. Therefore, it is preferred to add the stabilizer in such a manner that the pH of the aqueous solution of the specific dihydroxy compound containing the above-mentioned stabilizer becomes about 7.

[0129] When the amount of the alkaline stabilizer is too small, the effect of preventing the specific dihydroxy compound from deteriorating may not be obtained, and when it is too large, the specific dihydroxy compound may be modified. Therefore, the alkaline stabilizer is preferably 0.0001% by weight to 1% by weight, more preferably 0.001% by weight to 0.1% by weight, relative to each dihydroxy compound used in the present invention.

[0130] When the dihydroxy compound used in the present invention contains these basic stabilizers and is used directly as a raw material for producing a polycarbonate resin, the basic stabilizer itself becomes a polymerization catalyst, making it difficult to control the polymerization rate and quality and causing deterioration in the hue of the resin.

[0131] Therefore, when a basic stabilizer is contained in the specific dihydroxy compound or the other dihydroxy compound, it is preferred to remove the basic stabilizer by using an ion exchange resin or distillation before using the compound as a raw material for producing a polycarbonate resin.

[0132] The specific dihydroxy compound used in the present invention is easily and slowly oxidized by oxygen. Therefore, in order to prevent decomposition by oxygen during storage or handling during production, it is preferred to prevent water from mixing, use a deoxidizer, or place the compound under a nitrogen atmosphere.

[0133] (Carbonate Diester)

[0134] The polycarbonate resin in the present invention can be obtained by using a dihydroxy compound containing the above-mentioned specific dihydroxy compound and a carbonic acid diester as raw materials and polycondensing them by utilizing an ester exchange reaction. As the carbonic acid diester used, the carbonic acid diester shown in the following formula (10) can generally be cited. These carbonic acid diesters can be used alone or in combination of two or more.

[0135]

[0136] In the above formula (10), A 1 and A 2 are a substituted or unsubstituted aliphatic hydrocarbon group having 1 to 18 carbon atoms, or a substituted or unsubstituted aromatic hydrocarbon group, A 1 With A 2 Can be the same or different. 1 and A 2 It is preferably a substituted or unsubstituted aromatic hydrocarbon group, and more preferably an unsubstituted aromatic hydrocarbon group.

[0137] Examples of the carbonic acid diester represented by the formula (10) include diphenyl carbonate (DPC), substituted diphenyl carbonates such as ditolyl carbonate, dimethyl carbonate, diethyl carbonate, and di-tert-butyl carbonate, etc. Among them, diphenyl carbonate or substituted diphenyl carbonates are preferred, and diphenyl carbonate is particularly preferred.

[0138] The carbonic acid diester may contain impurities such as chloride ions. Impurities may inhibit the polymerization reaction or deteriorate the hue of the obtained polycarbonate resin. Therefore, it is preferable to use the carbonic acid diester purified by distillation or the like as necessary.

[0139] <Transesterification catalyst>

[0140] The polycarbonate resin in the present invention is produced by subjecting the above-mentioned dihydroxy compound to an ester exchange reaction with a carbonic acid diester. More specifically, the polycarbonate resin is obtained by subjecting the dihydroxy compound to an ester exchange reaction and removing the by-produced monohydroxy compound and the like to the outside of the system.

[0141] During the above-mentioned transesterification reaction, polycondensation is carried out in the presence of a transesterification catalyst. The transesterification catalyst (hereinafter sometimes simply referred to as catalyst or polymerization catalyst) that can be used in the production of the polycarbonate resin in the present invention may have a very large influence on the reaction rate or the quality of the polycarbonate resin obtained by polycondensation.

[0142] The catalyst used is not limited as long as it satisfies the transparency, hue, heat resistance, weather resistance and mechanical strength of the manufactured polycarbonate resin. For example, metal compounds of Group 1 or Group 2 (hereinafter simply referred to as "Group 1" or "Group 2") in the long-period periodic table, and basic compounds such as basic boron compounds, basic phosphorus compounds, basic ammonium compounds and amine compounds can be cited. Group 1 metal compounds and / or Group 2 metal compounds are preferably used.

[0143] Examples of the Group 1 metal compound include sodium hydroxide, potassium hydroxide, lithium hydroxide, cesium hydroxide, sodium hydrogen carbonate, potassium hydrogen carbonate, lithium hydrogen carbonate, cesium hydrogen carbonate, sodium carbonate, potassium carbonate, lithium carbonate, cesium carbonate, sodium acetate, potassium acetate, lithium acetate, cesium acetate, sodium stearate, potassium stearate, lithium stearate, cesium stearate, sodium borohydride, potassium borohydride, lithium borohydride, cesium borohydride, sodium phenylboronate, potassium phenylboronate, lithium phenylboronate, cesium phenylboronate, sodium benzoate, potassium benzoate, lithium benzoate, cesium benzoate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, dilithium hydrogen phosphate, dicesium hydrogen phosphate, disodium phenyl phosphate, dipotassium phenyl phosphate, dilithium phenyl phosphate, dicesium phenyl phosphate, sodium, potassium, lithium, cesium alkoxide, phenolate, disodium salt, dipotassium salt, dilithium salt and dicesium salt of bisphenol A, and the like. Among them, lithium compounds are preferred from the viewpoint of polymerization activity and the hue of the obtainable polycarbonate resin.

[0144] Examples of the Group 2 metal compound include calcium hydroxide, barium hydroxide, magnesium hydroxide, strontium hydroxide, calcium hydrogen carbonate, barium hydrogen carbonate, magnesium hydrogen carbonate, strontium hydrogen carbonate, calcium carbonate, barium carbonate, magnesium carbonate, strontium carbonate, calcium acetate, barium acetate, magnesium acetate, strontium acetate, calcium stearate, barium stearate, magnesium stearate, and strontium stearate.

[0145] Among them, a magnesium compound, a calcium compound or a barium compound is preferred. From the viewpoint of polymerization activity and the hue of the obtainable polycarbonate resin, a magnesium compound and / or a calcium compound is more preferred, and a calcium compound is most preferred.

[0146] It should be noted that, together with the aforementioned Group 1 metal compounds and / or Group 2 metal compounds, basic compounds such as basic boron compounds, basic phosphorus compounds, basic ammonium compounds, and amine compounds may be used in combination as an auxiliary, but it is particularly preferred to use only Group 1 metal compounds and / or Group 2 metal compounds.

[0147] Examples of the basic boron compound include sodium salts, potassium salts, lithium salts, calcium salts, barium salts, magnesium salts, or strontium salts of tetramethylboron, tetraethylboron, tetrapropylboron, tetrabutylboron, trimethylethylboron, trimethylbenzylboron, trimethylphenylboron, triethylmethylboron, triethylbenzylboron, triethylphenylboron, tributylbenzylboron, tributylphenylboron, tetraphenylboron, benzyltriphenylboron, methyltriphenylboron, and butyltriphenylboron.

[0148] Examples of the basic phosphorus compound include triethylphosphine, tri-n-propylphosphine, triisopropylphosphine, tri-n-butylphosphine, triphenylphosphine, tributylphosphine, and quaternary phosphonium salts.

[0149] Examples of the alkaline ammonium compound include tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, trimethylethylammonium hydroxide, trimethylbenzylammonium hydroxide, trimethylphenylammonium hydroxide, triethylmethylammonium hydroxide, triethylbenzylammonium hydroxide, triethylphenylammonium hydroxide, tributylbenzylammonium hydroxide, tributylphenylammonium hydroxide, tetraphenylammonium hydroxide, benzyltriphenylammonium hydroxide, methyltriphenylammonium hydroxide, and butyltriphenylammonium hydroxide.

[0150] Examples of the aforementioned amine compounds include 4-aminopyridine, 2-aminopyridine, N,N-dimethyl-4-aminopyridine, 4-diethylaminopyridine, 2-hydroxypyridine, 2-methoxypyridine, 4-methoxypyridine, 2-dimethylaminoimidazole, 2-methoxyimidazole, imidazole, 2-mercaptoimidazole, 2-methylimidazole, aminoquinoline and guanidine.

[0151] The amount of the polymerization catalyst used is preferably 0.1 μmol to 300 μmol, more preferably 0.5 μmol to 100 μmol, particularly preferably 1 μmol to 50 μmol, per 1 mol of all dihydroxy compounds used in the polymerization.

[0152] When a compound containing at least one metal selected from a group consisting of two groups in the long-period periodic table and lithium is used, in particular, when a magnesium compound and / or a calcium compound is used, the metal amount is preferably set to 0.1 μmol or more, more preferably 0.3 μmol or more, and particularly preferably 0.5 μmol or more per 1 mol of the total dihydroxy compound. The upper limit is preferably 20 μmol or less, more preferably 10 μmol or less, further preferably 5 μmol or less, and particularly preferably 3 μmol or less.

[0153] When the amount of catalyst is too small, the polymerization rate slows down. Therefore, in order to obtain a polycarbonate resin with a desired molecular weight, the polymerization temperature must be increased accordingly. For this reason, the color of the obtained polycarbonate resin is more likely to deteriorate. In addition, unreacted raw materials volatilize during the polymerization, and the molar ratio of the dihydroxy compound to the carbonic acid diester is destroyed, which may not reach the desired molecular weight. On the other hand, when the amount of the polymerization catalyst is too much, undesirable side reactions occur, which may lead to the deterioration of the color of the obtained polycarbonate resin or the coloration of the resin during molding.

[0154] However, when sodium, potassium or cesium among Group 1 metals is contained in a large amount in the polycarbonate resin, there is a possibility that the color may be adversely affected. Moreover, these metals are mixed not only from the catalyst used, but also from the raw materials or the reaction device. Regardless of the source, the total amount of these metal compounds in the polycarbonate resin is preferably 1 ppm by weight or less, and more preferably 0.5 ppm by weight or less in terms of the metal amount.

[0155] <Method for producing polycarbonate resin>

[0156] The polycarbonate resin in the present invention is obtained by polycondensing a dihydroxy compound including a specific dihydroxy compound and a carbonic acid diester by an ester exchange reaction.

[0157] The dihydroxy compound and the carbonic acid diester as raw materials are preferably uniformly mixed before the transesterification reaction. The mixing temperature is usually 80°C or higher, preferably 90°C or higher. In addition, the upper limit is usually 250°C or lower, preferably 200°C or lower, and more preferably 150°C or lower. Among them, it is preferably 100°C or higher and 120°C or lower.

[0158] When the mixing temperature is too low, the melting rate may be slow or the solubility may be insufficient, often resulting in problems such as solidification. When the mixing temperature is too high, the dihydroxy compound may be thermally degraded, resulting in the possibility of adversely affecting the hue and thermal stability of the obtained polycarbonate resin.

[0159] The mixing of the dihydroxy compound containing the specific dihydroxy compound as the raw material of the polycarbonate resin in the present invention and the carbonic acid diester is preferably carried out in an atmosphere with an oxygen concentration of 10 vol% or less, more preferably 0.0001 vol% to 10 vol%, further preferably 0.0001 vol% to 5 vol%, and particularly preferably 0.0001 vol% to 1 vol%. By being in the above range, deterioration of hue can be prevented.

[0160] In order to obtain the polycarbonate resin in the present invention, the carbonic acid diester is preferably used at a molar ratio of 0.94 to 1.04, more preferably 0.98 to 1.02, and even more preferably 1.00 to 1.01, relative to all dihydroxy compounds including the specific dihydroxy compound used in the reaction. When the molar ratio becomes smaller, the terminal phenyl group of the produced polycarbonate resin decreases, which easily causes poor appearance during molding.

[0161] In addition, when the molar ratio increases, the rate of the transesterification reaction may decrease, or it may be difficult to produce a polycarbonate resin having a desired molecular weight. The decrease in the rate of the transesterification reaction increases the thermal history during the polymerization reaction, and as a result, there is a possibility that the color and weather resistance of the obtained polycarbonate resin may deteriorate.

[0162] Furthermore, when the molar ratio of the carbonate diester relative to all dihydroxy compounds including the specific dihydroxy compound increases, the amount of residual carbonate diester and the compound represented by the above formula (3) in the obtained polycarbonate resin increases, which may cause problems such as contamination during molding, odor, and poor appearance.

[0163] In the present invention, the method of polycondensing the dihydroxy compound and the carbonic acid diester is carried out in the presence of the above-mentioned catalyst, usually using multiple reactors in multiple stages. The reaction form can be any method of batch type, continuous type, or a combination of batch type and continuous type. Preferably, the continuous type is used, which can obtain the polycarbonate resin with less heat history and excellent productivity.

[0164] Preferably, in the initial stage of polymerization, a prepolymer is obtained at a relatively low temperature and a low vacuum, and in the later stage of polymerization, a relatively high temperature and a high vacuum are used to increase the molecular weight to a predetermined value. In addition, from the viewpoint of controlling the polymerization rate and the quality of the obtained polycarbonate resin, it is important to appropriately select the jacket temperature and the internal temperature and the pressure in the reaction system at each molecular weight stage.

[0165] For example, if either the temperature or the pressure is changed too quickly before the polymerization reaction reaches a predetermined value, unreacted monomers may be distilled out, disrupting the molar ratio of the dihydroxy compound to the carbonic acid diester, resulting in a decrease in the polymerization rate, or failing to obtain a polymer having a predetermined molecular weight or terminal groups. As a result, there is a possibility that the purpose of the present invention cannot be achieved.

[0166] Furthermore, in order to suppress the amount of monomers distilled off, it is effective to use a reflux condenser in the polymerization reactor, and this effect is particularly great in a reactor at the initial stage of polymerization where there is a large amount of unreacted monomer components. The temperature of the refrigerant introduced into the reflux condenser can be appropriately selected according to the monomers used. Usually, the temperature of the refrigerant introduced into the reflux condenser is 45 to 180° C., preferably 80 to 150° C., and particularly preferably 100 to 130° C. at the inlet of the reflux condenser.

[0167] When the temperature of the refrigerant is too high, the reflux amount is reduced and its effect is reduced. On the contrary, when the temperature of the refrigerant is too low, there is a tendency that the efficiency of distillation removal of the monohydroxy compound that should be distilled off is reduced. As the refrigerant, warm water, steam, heat medium oil, etc. are used, preferably steam and heat medium oil.

[0168] The selection of the type and amount of the catalyst is important in order to appropriately maintain the polymerization rate, suppress the distillation of the monomers, and not to deteriorate the color of the final polycarbonate resin. The polycarbonate resin in the present invention is preferably produced by polymerization in multiple stages using a catalyst and multiple reactors.

[0169] The reason for implementing polymerization with multiple reactors is that, in the initial stage of polymerization reaction, there are many monomers contained in the reaction solution, therefore, it is important to maintain the desired polymerization rate and suppress the volatilization of the monomers, and in the later stage of polymerization reaction, in order to shift the equilibrium to the polymerization side, it is important to fully distill and remove the by-product monohydroxy compound. Thus, when setting different polymerization reaction conditions, it is preferred to use multiple polymerization reactors configured in series from the viewpoint of production efficiency.

[0170] As described above, the number of reactors used in the production of the polycarbonate resin in the present invention is at least 2. From the viewpoint of production efficiency, the number is preferably 3 or more, more preferably 3 to 5, and particularly preferably 4. In the present invention, if there are 2 or more reactors, the reactor may further have a plurality of reaction stages with different conditions, and the temperature and pressure may be continuously changed.

[0171] In the present invention, the polymerization catalyst may be added to the raw material preparation tank, the raw material storage tank, or may be directly added to the polymerization tank. From the viewpoint of supply stability and polymerization control, a catalyst supply line is provided in the middle of the raw material line before supplying to the polymerization tank, and it is preferably supplied in an aqueous solution.

[0172] When the polymerization temperature is too low, productivity is reduced and the thermal history of the product is increased. When it is too high, not only the monomers are volatilized, but also the decomposition and coloration of the polycarbonate resin are promoted. Specifically, in the first step reaction, the internal temperature of the polymerization reactor is 130 to 210°C, preferably 150 to 205°C, and more preferably 170 to 200°C.

[0173] The reaction system is subjected to a pressure (absolute pressure) of 1 to 110 kPa, preferably 5 to 70 kPa, and more preferably 7 to 30 kPa (absolute pressure), and the reaction time is 0.1 to 10 hours, preferably 0.5 to 3 hours, while the generated monohydroxy compound is distilled out of the reaction system.

[0174] In the second step and after the second step, the pressure of the reaction system is gradually reduced from the pressure of the first step, and then the produced monohydroxy compound is discharged to the outside of the reaction system. In particular, in order to control the amount of the compound represented by the above formula (3), in the second step and after the second step, the pressure is set to 15 kPa or less, and finally, the pressure (absolute pressure) of the reaction system is set to 600 Pa or less, and the maximum internal temperature is 190 to 240°C, preferably 195 to 235°C, and the reaction is usually carried out for 0.1 to 5 hours, preferably 0.1 to 4 hours, and particularly preferably 0.5 to 3 hours.

[0175] In order to obtain a polycarbonate resin of a predetermined molecular weight, if the polymerization temperature is excessively increased or the polymerization time is prolonged, the color tone tends to deteriorate. In particular, in order to obtain a polycarbonate resin having a low content of the compound represented by the above formula (3) with suppressed coloration and thermal degradation, a good hue, and a high maximum internal temperature in all reaction stages is preferably lower than 240°C, particularly preferably 210 to 235°C.

[0176] In addition, when the internal temperature in all reaction stages is above 210°C and below 240°C, the reaction time is less than 3 hours, because the coloring and thermal degradation of the polycarbonate resin can be suppressed, a polycarbonate resin with good hue can be obtained, and the production amount of the compound represented by the above formula (3) can be controlled. Therefore, it is preferred, and particularly preferred to be within 2.5 hours.

[0177] In addition, in order to suppress the decrease in the polymerization rate in the second half of the polymerization reaction and minimize the deterioration caused by the thermal history, it is preferred to use a horizontal reactor with excellent plug fluidity and interface renewal properties and excellent control of the compound represented by the above formula (3) in the final stage of the polymerization.

[0178] From the viewpoint of effective utilization of resources, the by-produced monohydroxy compound is preferably purified as necessary and then reused as a raw material for diphenyl carbonate, bisphenol A, or the like.

[0179] The polycarbonate resin in the present invention is generally cooled and solidified after polycondensation as described above, and pelletized using a rotary cutter or the like. The pelletization method is not limited, and the following methods may be mentioned: a method of taking out the resin in a molten state from the final polymerization reactor, cooling and solidifying it in the form of strands, and pelletizing it; a method of supplying the resin in a molten state from the final polymerization reactor to a single screw or twin screw extruder, melt extruding it, cooling and solidifying it, and pelletizing it; or a method of taking out the resin in a molten state from the final polymerization reactor, cooling and solidifying it in the form of strands, temporarily pelletizing it, and then supplying the resin to a single screw or twin screw extruder again, melt extruding it, cooling and solidifying it, and pelletizing it, etc.

[0180] When an extruder is used, residual monomers may be devolatilized under reduced pressure in the extruder, or commonly known heat stabilizers, neutralizers, ultraviolet absorbers, light stabilizers, release agents, colorants, antistatic agents, lubricants, lubricants, plasticizers, compatibilizers, flame retardants, etc. may be added to perform kneading.

[0181] The melt kneading temperature in the extruder depends on the glass transition temperature and molecular weight of the polycarbonate resin, and is generally 200 to 300° C., preferably 210 to 280° C., and more preferably 220 to 270° C. When the melt kneading temperature is lower than 200° C., the melt viscosity of the polycarbonate resin is high, the load on the extruder increases, and the productivity decreases. When the melt kneading temperature is higher than 300° C., the thermal degradation of the polycarbonate resin becomes severe, resulting in a decrease in mechanical strength due to a decrease in molecular weight, coloring, and the generation of bubbles due to gas generation during film molding.

[0182] The molecular weight of the polycarbonate resin of the present invention thus obtained can be expressed as a reduced viscosity. The reduced viscosity is usually 0.30 dL / g or more, preferably 0.35 dL / g or more. In addition, the upper limit of the reduced viscosity is usually 1.20 dL / g or less, preferably 1.00 dL / g or less, and more preferably 0.80 dL / g or less.

[0183] When the reduced viscosity of the polycarbonate resin is too low, the mechanical strength of the molded product may be low. In addition, when the reduced viscosity is too high, the fluidity during molding is reduced, and there is a tendency to reduce productivity and moldability. It should be noted that the reduced viscosity of the polycarbonate resin is measured as follows: using dichloromethane as a solvent, the concentration of the polycarbonate resin is precisely adjusted to 0.6 g / dL, and the temperature is 20.0°C ± 0.1°C, and the Ubbelohde viscosity tube is used for measurement. The details of the method for measuring the reduced viscosity are described in the items of the examples.

[0184] [Additives for polycarbonate resin]

[0185] <Phosphorus compounds>

[0186] The polycarbonate resin in the present invention preferably contains a phosphorus compound added to deactivate the polymerization catalyst and further to suppress coloration of the polycarbonate resin at high temperatures.

[0187] As the phosphorus compound, at least one selected from the group consisting of phosphoric acid, phosphorous acid, hypophosphorous acid, polyphosphoric acid, phosphonic acid, phosphonic acid esters, acidic phosphoric acid esters, and aliphatic cyclic phosphites is preferably used. Among the above, phosphorous acid, phosphonic acid, and phosphonic acid esters are more excellent in the effects of catalytic deactivation and coloration inhibition, and phosphonic acid esters are particularly preferred.

[0188] Examples of the phosphonic acid include phosphonic acid (phosphorous acid), methylphosphonic acid, ethylphosphonic acid, vinylphosphonic acid, decylphosphonic acid, phenylphosphonic acid, benzylphosphonic acid, aminomethylphosphonic acid, methylenediphosphonic acid, 1-hydroxyethane-1,1-diphosphonic acid, 4-methoxyphenylphosphonic acid, nitrilotri(methylenephosphonic acid), and propylphosphonic anhydride.

[0189] Examples of the phosphonic acid ester include dimethyl phosphonate, diethyl phosphonate, bis(2-ethylhexyl)phosphonate, dilauryl phosphonate, dioleyl phosphonate, diphenyl phosphonate, dibenzyl phosphonate, dimethyl methylphosphonate, diphenyl methylphosphonate, diethyl ethylphosphonate, diethyl benzylphosphonate, dimethyl phenylphosphonate, diethyl phenylphosphonate, dipropyl phenylphosphonate, diethyl (methoxymethyl)phosphonate, diethyl vinylphosphonate, and hydroxymethylphosphonate. Phosphonic acid diethyl ester, (2-hydroxyethyl) phosphonic acid dimethyl ester, p-methylbenzylphosphonic acid diethyl ester, diethyl phosphonoacetic acid, diethyl phosphonoethyl ester, diethyl phosphonoacetic acid tert-butyl ester, (4-chlorobenzyl) phosphonic acid diethyl ester, cyanophosphonic acid diethyl ester, cyanomethylphosphonic acid diethyl ester, 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid diethyl ester, diethyl phosphonoacetaldehyde diethyl acetal, (methylthiomethyl) phosphonic acid diethyl ester, etc.

[0190] Examples of the acidic phosphate include phosphoric acid diesters such as dimethyl phosphate, diethyl phosphate, divinyl phosphate, dipropyl phosphate, dibutyl phosphate, bis(butoxyethyl) phosphate, bis(2-ethylhexyl) phosphate, diisotridecyl phosphate, dioleyl phosphate, distearyl phosphate, diphenyl phosphate, and dibenzyl phosphate, or mixtures of diesters and monoesters, diethyl chlorophosphate, and zinc salts of stearyl phosphate.

[0191] Aliphatic cyclic phosphites are defined as phosphite compounds that do not contain aromatic groups in a cyclic structure containing a phosphorus atom. Examples thereof include bis(decyl)pentaerythritol diphosphite, bis(tridecyl)pentaerythritol diphosphite, distearylpentaerythritol diphosphite, bis(2,6-tert-butylphenyl)pentaerythritol diphosphite, bis(nonylphenyl)pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, hydrogenated bisphenol A·pentaerythritol phosphite polymers, and other polymer-type compounds formed from dihydroxy compounds and pentaerythritol diphosphites.

[0192] These may be used alone or in combination of two or more in any ratio.

[0193] When the content of the aforementioned phosphorus compound is too small, the effects of catalytic deactivation and coloration inhibition are insufficient. In addition, when the content of the aforementioned phosphorus compound is too large, the polycarbonate resin is instead colored, or coloration under hot and humid conditions occurs. Therefore, the content of the phosphorus compound is not particularly limited, and is preferably set to 0.02 wtppm or more and 0.7 wtppm or less, more preferably 0.05 wtppm or more and 0.65 wtppm or less, and particularly preferably 0.07 wtppm or more and 0.60 wtppm or less, based on the content of phosphorus atoms in the polycarbonate resin.

[0194] The phosphorus compound is usually prepared by using phosphorus trichloride as a starting material, so that the chlorine-containing components derived from the unreacted product and the hydrochloric acid that has been separated sometimes remain, but the amount of chlorine atoms contained in the phosphorus compound is preferably less than 5% by weight. When the residual amount of chlorine atoms is large, there is the following concern: the metal part of the manufacturing equipment to which the phosphorus compound is added is corroded, or the thermal stability of the polycarbonate resin is reduced, promoting the reduction of the molecular weight caused by coloring and thermal degradation.

[0195] As described above, the phosphorus compound is preferably added to the polycarbonate resin using an extruder and kneaded. In particular, it is most effective to directly supply the polycarbonate resin to the extruder in a molten state after polymerization and immediately add the phosphorus compound to the resin. Furthermore, when the catalyst is deactivated and devolatilization is performed from the vacuum exhaust port in the extruder, low molecular components can be effectively devolatilized and removed.

[0196] <Hindered phenol compounds>

[0197] The polycarbonate resin in the present invention contains a hindered phenol compound in addition to the above-mentioned phosphorus-based compound, and thus the color tone of the polycarbonate resin can be expected to be further improved.

[0198] Specific examples of hindered phenol compounds include 2,6-di-tert-butylphenol, 2,4-di-tert-butylphenol, 2-tert-butyl-4-methoxyphenol, 2-tert-butyl-4,6-dimethylphenol, 2,6-di-tert-butyl-4-methylphenol, 2,6-di-tert-butyl-4-ethylphenol, 2,5-di-tert-butylhydroquinone, n-octadecyl-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate, 2-tert-butyl-6-(3'-tert-butyl-5'-methyl-2'-hydroxybenzyl)-4-methylphenyl acrylate, 2,2'-methylene-bis-(4-methyl-6-tert-butylphenol), 2,2'-methylene-bis-(6-cyclohexyl-4- methylphenol), 2,2'-ethylidene-bis-(2,4-di-tert-butylphenol), tetrakis-[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]-methane, n-octadecyl-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate, 1,3,5-trimethyl-2,4,6-tris-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, triethylene glycol-bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate], 1,6-hexanediol-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], pentaerythritol-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], etc.

[0199] These may be used alone or in combination of two or more in any ratio.

[0200] The content of the hindered phenol compound in the polycarbonate resin of the present invention is preferably 0.001 to 1 part by weight, more preferably 0.005 to 0.5 part by weight, and even more preferably 0.01 to 0.3 part by weight, based on 100 parts by weight of the polycarbonate resin.

[0201] In addition, hindered phenol compounds and the following antioxidants are preferably added to the polycarbonate resin and kneaded using an extruder, similarly to the phosphorus-based compounds.

[0202] <Antioxidants>

[0203] For the purpose of anti-oxidation, a generally known antioxidant may be added to the polycarbonate resin of the present invention.

[0204] Specific examples of the antioxidant include triphenyl phosphite, tris(nonylphenyl) phosphite, tris(2,4-di-tert-butylphenyl) phosphite, tridecyl phosphite, trioctyl phosphite, trioctadecyl phosphite, didecyl monophenyl phosphite, dioctyl monophenyl phosphite, diisopropyl monophenyl phosphite, monobutyl diphenyl phosphite, monodecyl diphenyl phosphite, monooctyl diphenyl phosphite, 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite, tris(2,4-di-tert-butylphenyl) phosphite, tributyl phosphate, triethyl phosphate, trimethyl phosphate, triphenyl phosphate, diphenyl mono-o-biphenyl phosphate, dibutyl phosphate, dioctyl phosphate, and phosphite. diisopropyl ester, tetrakis(2,4-di-tert-butylphenyl) 4,4'-biphenylene diphosphonate, pentaerythritol tetrakis(3-mercaptopropionate), pentaerythritol tetrakis(3-laurylthiopropionate), glycerol-3-stearylthiopropionate, N,N-hexamethylenebis(3,5-di-tert-butyl-4-hydroxy-hydrocinnamic acid), tris(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanurate, tetrakis(2,4-di-tert-butylphenyl) 4,4'-biphenylene diphosphonate, 3,9-bis{1,1-dimethyl-2-[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl}-2,4,8,10-tetraoxaspiro(5,5)undecane, etc.

[0205] These antioxidants may be used alone or in combination of two or more.

[0206] The amount of these antioxidants to be added is preferably 0.0001 to 0.1 parts by weight, more preferably 0.0005 to 0.08 parts by weight, and even more preferably 0.001 to 0.05 parts by weight, based on 100 parts by weight of the polycarbonate resin.

[0207] <Bluing agent>

[0208] The polycarbonate resin in the present invention may contain a bluing agent.

[0209] The bluing agent used in the present invention can be appropriately selected from bluing agents generally used in polycarbonate resin compositions, and can be used by adjusting the amount thereof blended, and a plurality of bluing agents can be used.

[0210] Generally, when the polycarbonate resin (A) is 100 parts by weight, the content of the bluing agent in the polycarbonate resin is preferably 0.1×10 -4 ~10.0×10 -4 Parts by weight, more preferably 0.3×10 -4 ~5.0×10 -4 Parts by weight, particularly preferably 0.3×10 -4 ~2.0×10 -4Parts by weight.

[0211] If the content of bluing agent is 0.1×10 -4 10.0×10 wt. parts or more is preferred because it is easy to make the YI value of the polycarbonate resin plate in the present invention before and after the accelerated light resistance test within a specific range and the b* value 3 or less. On the other hand, if the content of the bluing agent is 10.0×10 -4 If the content is less than 50 parts by weight, the brightness will not be reduced, so that the L* value can be easily made 90 or more, which is preferred.

[0212] As the bluing agent used in the present invention, the bluing agent used in the polycarbonate resin composition can be suitably used. From the viewpoint of absorption wavelength, a dye having a maximum absorption wavelength of preferably 520 to 600 nm, more preferably 540 to 580 nm is used.

[0213] Specific examples of preferred anthraquinone-based bluing agents for use in the present invention include Solvent Violet 13 (generic name: CA. No. 60725; trade name: “Macrolex Violet B” manufactured by LANXESS Co., Ltd., “Dia Resin Blue G” manufactured by Mitsubishi Chemical Corporation, and “Sumiplast Violet B” manufactured by Sumitomo Chemical Co., Ltd.), Solvent Violet 14, Solvent Violet 31 (generic name: CA. No. 68210; trade name: “Dia Resin Violet D” manufactured by Mitsubishi Chemical Corporation), Solvent Violet 33 (CA. No. 60725; trade name: “Dia Resin Blue J” manufactured by Mitsubishi Chemical Corporation), Solvent Violet 36 (CA. No. 68210; trade name: “Macrolex Violet 3R” manufactured by LANXESS Co., Ltd.), Solvent Violet 40 (generic name: Blue45 [CA.No61110; trade name "Tetrazole Blue RLS" manufactured by SAND CO., LTD.], generic name Solvent Blue94 [CA.No61500; trade name "Dia Resin Blue N" manufactured by Mitsubishi Chemical Corporation], generic name Solvent Blue97 ["Macrolex BlueRR" manufactured by LANXESS Co., Ltd.], generic name Solvent Blue45, generic name Solvent Blue87 and generic name Disperse Violet28.

[0214] Among them, Solvent Violet 13 [Macrolex Violet B manufactured by LANXESS Co., Ltd.], Solvent Violet 36 [Macrolex Violet 3R manufactured by LANXESS Co., Ltd.], and Solvent Blue 97 [Macrolex Blue RR manufactured by LANXESS Co., Ltd.] are preferred, and Solvent Violet 13 [Macrolex Violet B manufactured by LANXESS Co., Ltd.] is more preferred.

[0215] Among them, the dye having a structure represented by the following formula (11), namely, the generic name Solvent Violet 13 [CA.No (Dye Index No.) 60725; trade names: “Macrolex Violet B” manufactured by LANXESS Co., Ltd., “Dia Resin Blue G” manufactured by Mitsubishi Chemical Corporation, and “Sumiplast Violet B” manufactured by Sumitomo Chemical Co., Ltd.] is particularly preferred.

[0216]

[0217] In the present invention, a pigment having a maximum absorption wavelength of preferably 520 to 600 nm, more preferably 540 to 580 nm may be used as a bluing agent, and the above-mentioned dye and pigment may be used in combination.

[0218] In the present invention, the bluing agent may be used alone or in combination of two or more. Preferably, the amount of the bluing agent used is small, and preferably the number of the bluing agents used is also small.

[0219] In the present invention, the mixing period and mixing method of the above-mentioned bluing agent compounded in the polycarbonate resin (A) are not particularly limited. As the mixing period, for example, the following methods can be cited: a method of adding it together with the raw materials before the polymerization reaction and directly polymerizing it; a method of compounding it in a pipe or an extruder at the end of the polymerization reaction; a method of compounding it when the polycarbonate resin and other compounding agents are melt-kneaded, etc. When melt-kneading and compounding are performed after the polymerization reaction is completed, the dispersion of the bluing agent is good and it is easy to take into account the adjustment of the b* value and the L* value, so it is preferred. The method of directly introducing it into the extruder in a molten state after the polycondensation reaction is completed, compounding the bluing agent and performing melt-kneading can minimize the influence of thermal history and oxygen mixing, so it is particularly preferred.

[0220] <Ultraviolet light absorber>

[0221] The ultraviolet absorber used in the present invention is not limited as long as it has the specific physical properties of the present invention and absorbs light in the ultraviolet wavelength region.

[0222] The melting point of the ultraviolet absorber used in the present invention is 135° C. or higher, more preferably 140° C. or higher, and even more preferably 145° C. or higher.

[0223] The melting point of the ultraviolet absorber used in the present invention is lower than 300° C., more preferably 290° C. or lower, and even more preferably 280° C. or lower.

[0224] By setting the melting point within this range, roll contamination and attachments on the T-die can be reduced during extrusion film-making, and the appearance of the film becomes good. At the same time, when the ultraviolet absorber is kneaded in an extruder, the particles of the ultraviolet absorber are completely melted and uniformly dispersed, thereby preventing the film appearance from being poor due to the particles of the ultraviolet absorber.

[0225] The 5% weight loss temperature of the ultraviolet absorber used in the present invention is higher than 240°C. It is preferably higher than 245°C, and more preferably higher than 250°C. By being within this range, the ultraviolet absorber can be prevented from decomposing during melt kneading. In this way, not only can the ability of the ultraviolet absorber be fully exerted, but also the decomposition products can be prevented from accumulating at the vent of the extrusion to hinder the continuous operation, or accumulating at the T die, rollers, etc. to damage the appearance of the film.

[0226] In the present invention, the ultraviolet absorber is contained in an amount exceeding 0.45 parts by weight, preferably exceeding 0.47 parts by weight, and more preferably exceeding 0.5 parts by weight, based on 100 parts by weight of the polycarbonate resin.

[0227] By being within this range, the target transmittance can be maintained in the ultraviolet region, and a desired effect can be obtained.

[0228] In addition, the ultraviolet absorber is contained in an amount of 7 parts by weight or less relative to 100 parts by weight of the polycarbonate resin. In addition, it is more preferably contained in an amount of 5 parts by weight or less, and further preferably contained in an amount of 3 parts by weight or less. By being within this range, not only the poor appearance of the film caused by roll contamination can be prevented, but also the increase of foreign matter caused by the aggregation of the ultraviolet absorber can be prevented.

[0229] When the ultraviolet absorber is attached to the roller, the unevenness is transferred to the film from the attached material, and the uniformity of the film thickness cannot be maintained. As a result, the thickness of the obtained film is uneven and the phase difference is uneven. As the thickness accuracy of the film, the preferred thickness accuracy in the width direction varies depending on the required physical properties of each application, and is usually within ±10%, preferably within ±5%, and particularly preferably within ±3%.

[0230] In addition, when the melting point of the ultraviolet absorber is within the above range and the amount added is within the above range, the glass transition temperature of the polycarbonate resin composition does not drop significantly after the ultraviolet absorber is added, and the heat resistance can be maintained. The temperature difference of the glass transition temperature of the composition relative to the glass transition temperature of the polycarbonate resin without adding the ultraviolet absorber is within 7°C, preferably within 5°C, and more preferably within 3°C.

[0231] Preferred ultraviolet absorbers include triazine-based, benzophenone-based, benzotriazole-based, quinolinone-based, benzoate-based, cyanoacrylate-based, and benzoxazole-based ultraviolet absorbers.

[0232] (Triazine UV absorber)

[0233] Examples of the triazine-based ultraviolet absorber include 2,4-diphenyl-6-(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,6-diphenyl-4-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, and 2,4-diphenyl-6-(2-hydroxy-4-octyloxyphenyl)-1,3,5 -triazine, 2,4-diphenyl-6-(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, oxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-ethoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-propoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-methoxycarbonylpropyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-ethoxycarbonylethyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-(1-(2-ethoxyhexyloxyphenyl))-1,3,5-triazine 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-propoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-octyl ...6-Tris(2-hydroxy-3-methyl-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-benzyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-propoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-methoxycarbonyl) propyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxycarbonylethyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-(1-(2-ethoxyhexyloxy)-1-oxopropane-2-yloxy)phenyl)-1,3,5-triazine, 2,4-bis(2,4-dimethylphenyl)-6-(2-hydroxy-4-N-octyloxyphenyl)-1,3,5-triazine, 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-(2-(2-ethylhexanoyloxy)ethoxy)phenol, etc.

[0234] Among them, commercially available products include 2,4-bis(2,4-dimethylphenyl)-6-(2-hydroxy-4-N-octyloxyphenyl)-1,3,5-triazine (“Kemisorb 102” manufactured by Chemipro Kasei Kaisha, Ltd.), 2,4,6-tris(2-hydroxy-3-methyl-4-hexyloxyphenyl)-1,3,5-triazine (“ADK STAB LA-F70” manufactured by Adeka Corporation), 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-(2-(2-ethylhexanoyloxy)ethoxy)phenol (“ADK STAB LA-46” manufactured by Adeka Corporation), and 2,4-diphenyl-6-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine (“Tinuvin 1577” manufactured by BASF Japan Co., Ltd.).

[0235] (Benzophenone-based UV absorber)

[0236] Examples of the benzophenone-based ultraviolet absorber include 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octyloxybenzophenone, 2-hydroxy-4-benzyloxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid trihydrate, 2-hydroxy-4-dodecyloxy-benzophenone, 2-hydroxy-4-octadecyloxy-benzophenone, 2,2'-dihydroxybenzophenone ...methoxybenzophenone-5-sulfonic acid trihydrate, 2-hydroxy-4-dodecyloxy-benzophenone, 2-hydroxy-4-octadecyloxy-benzophenone, 2,2'-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid trihydrate, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid trihydrate, 2-hydroxy-4-dodecyloxy-benzophenone, 2-hydroxy-4-octadecyloxy-benzo -4-methoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxy-5-sodium sulfonatebenzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2-hydroxy-4-n-dodecyloxybenzophenone, 2-hydroxy-4-methoxy-2'-carboxybenzophenone, 4,4'-bis(diethylamino)benzophenone, etc.

[0237] Among them, commercially available products include 2,2',4,4'-tetrahydroxybenzophenone ("SEESORB 106" manufactured by Shipro Kasei Kaisha, Ltd., "Uvinul 3050" manufactured by BASF Japan Co., Ltd.), and 2,2'-dihydroxy-4,4'-dimethoxybenzophenone ("SEESORB 107" manufactured by Shipro Kasei Kaisha, Ltd., "Uvinul 3049" manufactured by BASF Japan Co., Ltd.).

[0238] (Benzotriazole UV absorber)

[0239] Examples of the benzotriazole ultraviolet absorber include 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-[2'-hydroxy-3',2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 5'-bis(α,α-dimethylbenzyl)phenyl]-benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butyl-phenyl)-benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butyl- phenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-pentyl)-benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-pentylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(3",4",5",6"-tetrahydrophthalimidomethyl)-5'-methylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-pentylphenyl), 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], etc.

[0240] Among them, commercially available products include 2,2′-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol] (“ADK STAB LA-31” manufactured by ADEKA CORPORATION, “Kemisorb 279” manufactured by CHEMIPRO KASEI KAISHA, LTD.), and 2-(2′-hydroxy-5′-tert-octylphenyl)benzotriazole (“SEESORB 709” manufactured by Shipro Kasei Kaisha, Ltd.).

[0241] (Indole UV absorber)

[0242] As the indole ultraviolet absorber, a compound represented by the following formula (12) can be used, and examples thereof include 2-[(1-methyl-2-phenyl-1H-indol-3-yl)methylene]propane dinitrile ("BONASORB UA-3901" manufactured by Orient Chemical Industries Co., Ltd.).

[0243]

[0244] In the above formula (12), R1 to R3 represent any substituents. R2 and R3 may be substituted at one or more locations, and when substituted at more than one location, each substituent may be the same or different.

[0245] (Quinolinone UV absorber)

[0246] As the quinolinone ultraviolet absorber, a compound represented by the following formula (13) can be used, and examples thereof include 4-hydroxy-3-[(phenylimino)methyl]-2(1H)-quinolinone ("BONASORB UA-3701" manufactured by Orient Chemical Industries Co., Ltd.).

[0247]

[0248] In the above formula (13), R4 to R6 represent any substituents. R5 and R6 may be substituted at one or more locations, and when substituted at more than one location, each substituent may be the same or different.

[0249] (Benzoate-based UV absorber)

[0250] Examples of the benzoate-based ultraviolet absorbers include 2,4-di-tert-butylphenyl-3',5'-di-tert-butyl-4'-hydroxybenzoate, 2,6-di-tert-butylphenyl-3',5'-di-tert-butyl-4'-hydroxybenzoate, n-hexadecyl-3,5-di-tert-butyl-4-hydroxybenzoate, n-octadecyl-3,5-di-tert-butyl-4-hydroxybenzoate, etc. These benzoate-based ultraviolet absorbers can be used as ultraviolet absorbers.

[0251] (Cyanoacrylate UV absorber)

[0252] Examples of the cyanoacrylate ultraviolet absorber include 2'-ethylhexyl-2-cyano-3,3-diphenylacrylate, ethyl-2-cyano-3-(3',4'-methylenedioxyphenyl)-acrylate, etc. These cyanoacrylate ultraviolet absorbers can be used as the ultraviolet absorber.

[0253] In the present invention, the ultraviolet absorber may be used alone or in combination of two or more.

[0254] Among them, triazine-based, benzotriazole-based, quinolinone-based, and indole-based compounds are preferred from the viewpoint of thermal stability and little coloration of the resin.

[0255] (Other UV absorbers)

[0256] In addition to the above-mentioned ultraviolet absorbers, fluorescent whitening agents may also be used as other ultraviolet absorbers. Examples thereof include 7-(dimethylamino)-4-methylcoumarin, benzoxazole-based 2,5-bis(5-tert-butyl-2-benzoxazolyl)thiophene (BASF Japan Co., Ltd. "TINOPAL OB"), and 4,4'-bis(2-benzoxazolyl)stilbene. Among them, benzoxazole-based agents are preferred.

[0257] [Polycarbonate resin composition]

[0258] The polycarbonate resin composition of the present invention can also be mixed with one or more synthetic resins such as aromatic polycarbonate resins, aromatic polyesters, aliphatic polyesters, polyamides, polystyrenes, polyolefins, acrylic acid, amorphous polyolefins, ABS, AS, etc., biodegradable resins such as polylactic acid and polystyrene succinate, rubber, etc., and used in the form of a polymer alloy.

[0259] Furthermore, the polycarbonate resin used in the present invention can be added with these other resin components and a nucleating agent, flame retardant, flame retardant aid, inorganic filler, impact modifier, hydrolysis inhibitor, foaming agent, dye pigment, etc. commonly used in resin compositions to form a polycarbonate resin composition.

[0260] [Method for producing polycarbonate resin extrusion molded product]

[0261] <Manufacturing method>

[0262] The polycarbonate resin film of the present invention is a film obtained by molding a resin composition containing a polycarbonate resin used in the present invention, an ultraviolet absorber, and other additives as required according to a conventional method. The polycarbonate resin film is preferably manufactured by a melt extrusion molding method such as a T-die molding method and an inflation molding method, and is particularly preferably a T-die molding method.

[0263] When the polycarbonate resin film of the present invention is placed on the front or back of an image display device, the displayed image is damaged and cannot be viewed due to defects, distortion, etc. Therefore, when the film is made into a film by melt extrusion molding, it is required to have very few foreign matter and bad spots originating from the resin, such as gel, bubbles, and yellowing, and to have a uniform thickness in the width direction and no optical distortion such as local phase difference.

[0264] The resin temperature during melt extrusion molding is usually in the range of 150 to 265°C, preferably 200 to 260°C, and particularly preferably 210 to 250°C. When the temperature is lower than the above, the melt viscosity tends to be too high and the extrusion load tends to be high. On the other hand, when the temperature is higher than the above, at least the polycarbonate resin in the resin composition begins to thermally decompose, resulting in deterioration phenomena such as coloring and viscosity reduction.

[0265] On the basis of controlling the resin temperature to make it a melt viscosity suitable for molding, the discharge amount of the raw material feeder, the screw speed of the extruder, the liquid delivery amount of the gear pump, etc. are mutually feedback-controlled to make the resin extrusion straightened, thereby improving the thickness accuracy of the film. The preferred thickness accuracy in the width direction varies according to the required physical properties of each application, and is usually within ±10%, preferably within ±5%, and particularly preferably within ±3%.

[0266] When there is a traverse type continuous thickness measuring machine in the continuous film production line, the thickness in the width direction is evaluated at each measuring point. When the film is sliced ​​online, the thickness is evaluated at points measured with a micrometer thickness gauge at intervals of 50 mm in the width direction. Here, the two ends of the extruded film become thicker due to shrinkage, etc., so it is evaluated within the width direction range excluding the part discarded by slitting.

[0267] The cooling roll temperature is preferably set to Tg-100°C to Tg+50°C, more preferably Tg-80°C to Tg+40°C, and particularly preferably Tg-60°C to Tg+30°C relative to the glass transition temperature (Tg) of the polycarbonate resin composition. More specifically, the cooling roll temperature is preferably 20 to 170°C, more preferably 40 to 160°C, and particularly preferably 60 to 150°C.

[0268] When the temperature of the cooling roller is lower than the above temperature, gear lines will appear on the film surface, or local optical distortion will become more obvious. On the other hand, when the temperature is higher than the above temperature, the extruded film will be difficult to peel off from the cooling roller, resulting in peel marks, or the roller will tend to be contaminated.

[0269] In addition, the polycarbonate resin film in the present invention may be a stretched film, and may be stretched in at least one direction to form a phase difference film.

[0270] As for the stretching method, various stretching methods such as free end stretching, fixed end stretching, free end shrinking, fixed end shrinking, etc. can be used alone, simultaneously or sequentially. In addition, the stretching direction can be carried out in various directions and dimensions such as horizontal direction, vertical direction, thickness direction, diagonal direction, etc., without particular limitation. Preferably, a transverse uniaxial stretching method, a longitudinal and transverse simultaneous biaxial stretching method, a longitudinal and transverse sequential biaxial stretching method, etc. can be cited.

[0271] As a stretching means, any appropriate stretching machine such as a tenter stretching machine and a biaxial stretching machine can be used.

[0272] The stretching temperature can be appropriately selected according to the purpose. The stretching is preferably carried out in the range of Tg-20°C to Tg+30°C, preferably Tg-10°C to Tg+20°C, and more preferably Tg-5°C to Tg+10°C, relative to the glass transition temperature (Tg) of the original film (i.e., the polycarbonate or its resin composition in the present invention as the film-making material of the original film). By selecting such conditions, the phase difference value tends to become uniform, and the film is not easy to become turbid. Specifically, the above-mentioned stretching temperature is 90°C to 210°C, more preferably 100°C to 200°C, and particularly preferably 100°C to 180°C.

[0273] The stretching ratio can be appropriately selected according to the purpose, and is set to 1 times when not stretched, preferably 1.1 times or more and 6 times or less, more preferably 1.5 times or more and 4 times or less, further preferably 1.8 times or more and 3 times or less, and particularly preferably 2 times or more and 2.5 times or less.

[0274] If the stretch ratio is too high, not only may breakage occur during stretching, but also the effect of suppressing changes in optical properties caused by long-term use under high temperature conditions may be reduced. If it is too low, the desired optical properties may not be imparted at the desired thickness.

[0275] The stretching speed can also be appropriately selected according to the purpose, and is generally 50% to 2000%, preferably 100% to 1500%, more preferably 200% to 1000%, and particularly preferably 250% to 500%, based on the distortion speed shown in the following formula. When the stretching speed is too high, it is possible to cause breakage during stretching or a large change in optical properties caused by long-term use under high temperature conditions. In addition, when the stretching speed is too low, not only the productivity is reduced, but also the stretching ratio must be excessively increased in order to obtain the desired phase difference.

[0276] Distortion rate (% / min) = {stretching speed (mm / min) / length of original film roll (mm)} × 100

[0277] Furthermore, after stretching, a heat setting treatment may be performed in a heating furnace, or a relaxation step may be performed by controlling the width of a tenter or adjusting the peripheral speed of a roll.

[0278] By performing this treatment, changes in optical characteristics caused by long-term use under high-temperature conditions can be suppressed.

[0279] The film of the present invention can be produced by appropriately selecting and adjusting the treatment conditions in such a stretching step.

[0280] The upper limit of the thickness of the film of the present invention is 120 μm or less. It is more preferably 50 μm or less, and further preferably 30 μm or less. By setting the upper limit of the thickness of the film within this range, a film of the same area can be formed with less film-forming material, which is effective. Furthermore, the thickness of the product using the film can be maintained thinner, and the uniformity can be controlled, which is useful for equipment requiring precision, thinness, and homogeneity.

[0281] On the other hand, the lower limit of the thickness of the film of the present invention is 5 μm or more. Preferably, it is 10 μm or more. When the thickness of the film is too thin, the film handling becomes extremely difficult, wrinkles are generated during manufacturing, or it is sometimes difficult to stick with other films, sheets, etc. such as protective films. By setting the lower limit of the thickness of the film of the present invention within this range, such problems can be solved.

[0282] The film of the present invention can be used as a polarizer protective film, and can be hard-coated, treated for the purpose of anti-reflection, anti-stickiness, diffusion and even anti-glare. Before bonding, it can also be subjected to corona discharge treatment, ultraviolet irradiation treatment, etc. as a surface treatment.

[0283] The lower limit of the transmittance of the film of the present invention at a wavelength of 380 nm is 0.001% or more, preferably 0.005% or more, more preferably 0.008% or more, and further preferably 0.01% or more. When the transmittance is too low, the content of the ultraviolet absorber will inevitably increase, and there is a possibility of poor appearance of the film.

[0284] In addition, the upper limit of the transmittance of the film of the present invention at a wavelength of 380 nm is 15% or less, preferably 8% or less, more preferably 1% or less, and further preferably 0.1% or less. When the transmittance is too high, there is a concern that the polarizer may be degraded by ultraviolet rays when used as a polarizer protective film.

[0285] When the film of the present invention is used as a retardation film, the in-plane retardation at 548 nm is preferably 100 nm or more, more preferably 110 nm or more, and further preferably 120 nm or more.

[0286] In addition, it is preferably 200 nm or less, more preferably 180 nm or less, and further preferably 160 nm or less. When the in-plane phase difference is within this range, the quality of the image obtained by using the polarizing plate and the image display device of the present invention is extremely clear and good. Specifically, when the polarizing plate and the image display device obtained by using the present invention are observed through polarized sunglasses, rainbow patterns and the like generated due to changes in the visual angle are not easily generated.

[0287] <Foreign matter in film>

[0288] The generation of foreign matter in the film not only deteriorates the quality of the film, but is also undesirable from the viewpoint of the productivity of the film. In order to reduce foreign matter in the film, as mentioned above, it is particularly effective to reduce the content of specific compounds in the resin composition, prevent the generation of unmelted matter during melt kneading, and prevent the generation of film-forming roll contamination due to seepage during film forming.

[0289] The foreign matter in the film is evaluated by the method described below, preferably 15 pieces / m 2 Less than 10 pieces / m 2 Below, more preferably 5 / m 2 Below, especially preferably 3 pieces / m 2 If the amount of foreign matter exceeds this value, it will not only damage the appearance of the film, but also have a significant impact on the optical properties of the film.

[0290] Example

[0291] Hereinafter, the present invention will be described in further detail based on examples, but the present invention is not limited to the following examples unless the gist of the present invention is exceeded.

[0292] [Evaluation method]

[0293] Hereinafter, the physical properties and characteristics of the polycarbonate resin were evaluated by the following methods.

[0294] (1) Determination of reduced viscosity

[0295] A polycarbonate resin sample was dissolved in dichloromethane to prepare a polycarbonate resin solution with a concentration of 0.6 g / dL. The relative viscosity η was calculated from the solvent passage time t0 and the solution passage time t using the following formula (i) using an Ubbelohde viscometer manufactured by Moritomo Rika Kogyo Co., Ltd. at a temperature of 20.0°C ± 0.1°C. rel , according to the relative viscosity η rel , the specific viscosity η is calculated by the following formula (ii): sp .

[0296] η rel =t / t0···(i)

[0297] η sp =(η-η0) / η0=η rel -1···(ii)

[0298] The specific viscosity η sp Divide by the concentration c (g / dL) to find the reduced viscosity η sp / c. The higher the value, the greater the molecular weight. The greater the value of reduced viscosity, the better the mechanical strength of the film can be obtained.

[0299] (2) Ultraviolet transmittance at 380nm

[0300] The light transmittance at a wavelength of 380 nm was measured in accordance with JIS K0115 (2004) (General Rules for Absorptiometry) using an ultraviolet-visible spectrophotometer (U2900 manufactured by Hitachi High-Technologies Corporation).

[0301] (3) 5% weight loss temperature

[0302] Using TG-DTA6300 (manufactured by Seiko), about 10 mg of a sample was measured while heating from room temperature to 500° C. at 10° C. / min under nitrogen (flow rate 200 ml / min), and the 5% weight loss temperature was determined.

[0303] (4) Melting point

[0304] The measurement was performed using a differential scanning calorimeter (DSC6220 manufactured by SII NanoTechnology Inc.). About 10 mg of the sample was placed in an aluminum pan manufactured by the same company and sealed, and the temperature was raised from room temperature to 400°C at a heating rate of 10°C / min under a nitrogen flow of 50 mL / min to determine the temperature of the top of the melting peak.

[0305] (5) Glass transition temperature (Tg) of polycarbonate resin

[0306] The glass transition temperature of the polycarbonate resin is measured using a differential scanning calorimeter (DSC6220 manufactured by SII NanoTechnology Inc.). About 10 mg of the polycarbonate resin sample is placed in an aluminum pan manufactured by the same company and sealed, and the temperature is raised from room temperature to 250°C at a heating rate of 20°C / min under a nitrogen gas flow of 50 mL / min. After maintaining the temperature for 3 minutes, cool to 0°C at a rate of 20°C / min. Maintain at 0°C for 3 minutes, and heat to 200°C at a rate of 20°C / min again. Based on the DSC data obtained in the second heating, the glass transition start temperature is extrapolated.

[0307] (6) Determination of the content of phenol and the compound represented by formula (3)

[0308] About 1 g of a polycarbonate resin sample was precisely weighed and dissolved in 5 mL of dichloromethane to prepare a solution, and then acetone was added to a total of 25 mL to perform reprecipitation treatment. Next, the treated solution was filtered with a 0.2 μm disk filter and quantified by liquid chromatography.

[0309]

[0310] (7) Film forming and roller contamination evaluation

[0311] The film was formed into films of various thicknesses at 2 kg / hour using a gel counter FSA film inspection line manufactured by OCS Co., Ltd. (barrel setting temperature: 240°C, T-die (width 150 mm, setting temperature: 240°C), cooling roller (setting temperature: 105°C)), and the presence or absence of roller contamination was determined based on the following criteria.

[0312] The case where roller contamination can be visually confirmed within 0 minutes or more and less than 15 minutes: ××

[0313] Roller contamination can be visually confirmed within 15 minutes or more and less than 30 minutes: ×

[0314] If the roller contamination can be visually confirmed within 30 minutes or more and less than 60 minutes: △ -

[0315] The case where roller contamination can be visually confirmed within 60 minutes or more and less than 90 minutes: △

[0316] The case where roller contamination can be visually confirmed within 90 minutes or more and less than 120 minutes: ○ -

[0317] The case where roller contamination can be visually confirmed within 120 minutes or more and less than 150 minutes: ○

[0318] The roller contamination can be visually confirmed within 150 minutes or more and less than 180 minutes: ◎

[0319] (8)Thickness and thickness accuracy of the film

[0320] Starting from the obtained film, at about 10m, from the center of the film, for a range of 30mm in both width directions, at intervals of 10mm in the TD direction, a contact thickness gauge (manufactured by Ono Sakki Co., Ltd., product name "Digital Linear Gauge DG-933") was used to measure the thickness of the film. Here, the so-called "thickness of the film" in the present invention refers to the calculation of the total average of the above-mentioned measured values. In addition, the value obtained by the following formula is referred to as the so-called "thickness accuracy" in the present invention.

[0321] Thickness accuracy (%) = {(maximum deviation from the thickness of the film) / (thickness of the film)}×100

[0322] (In the formula, "the maximum deviation from the thickness of the film" refers to the maximum value of the difference between the above-mentioned respective measured values ​​and the average value (thickness of the film).)

[0323] The smaller the numerical value of the thickness accuracy is, the more uniform the thickness of the film is.

[0324] (9) Foreign matter in thin film

[0325] The obtained film was cut into a sample with a width of 50 mm and a length of 200 mm, and the number of foreign particles with a diameter (longer diameter in the case of an ellipse) of 150 μm or more in the sample was visually counted. The fewer the number of foreign particles, the better the film is when used as an optical film.

[0326] [Raw materials used]

[0327] The abbreviations and manufacturers of the compounds used in the following Examples and Comparative Examples are as follows.

[0328] <Dihydroxy compounds>

[0329] ·ISB: Isosorbide [manufactured by Frodo Co., Ltd.]

[0330] ·CHDM: 1,4-cyclohexanedimethanol [SK Chemical Co., Ltd.]

[0331] ·TCDDM: Tricyclodecane dimethanol [manufactured by OXEA Co., Ltd.]

[0332] <Carbonate diester>

[0333] ·DPC: diphenyl carbonate [manufactured by Mitsubishi Chemical Corporation]

[0334] <Hindered phenol compounds>

[0335] ·Irganox 1010: Pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] [manufactured by BASF Japan Co., Ltd.]

[0336] <Phosphorus compounds>

[0337] Phosphorous acid [produced by Taihei Chemical Industry Co., Ltd.] (molecular weight 82.0)

[0338] ·AS2112: Tris(2,4-di-tert-butylphenyl)phosphite [manufactured by ADEKA Co., Ltd.] (molecular weight 646.9)

[0339] <Ultraviolet light absorber>

[0340] · UVA-1: LA-31 [manufactured by ADEKA Co., Ltd.]

[0341] · UVA-2: LA-36 [manufactured by ADEKA Co., Ltd.]

[0342] · UVA-3: LA-F70 [manufactured by ADEKA Co., Ltd.]

[0343] · UVA-4: BONASORB UA-3701 [manufactured by Orient Chemical Industries Co., Ltd.]

[0344] ·UVA-5: Uvinul 3049 [manufactured by BASF Japan Co., Ltd.]

[0345] ·UVA-6: Uvinul 3050 [manufactured by BASF Japan Co., Ltd.]

[0346] · UVA-7: Seesorb709 [manufactured by Shipro Kasei Kaisha, Ltd.]

[0347] ·UVA-8: Tinuvin234 [manufactured by BASF Japan Co., Ltd.]

[0348] ·UVA-9: TINOPAL OB [manufactured by BASF Japan Co., Ltd.]

[0349] UVA-10: Cyasorb UV-5411 [made by Cytec Industries Inc., Japan]

[0350] The physical properties of the ultraviolet absorber are summarized in Table 1 below.

[0351] [Table 1]

[0352]

[0353] Method for producing polycarbonate resin

[0354] [Production Example 1]

[0355] Polymerization of polycarbonate resin was carried out using a continuous polymerization device consisting of three vertical stirring reactors, one horizontal stirring reactor, and a twin-screw extruder. ISB, CHDM, and DPC were melted in tanks, respectively, and continuously supplied to the first vertical stirring reactor at a molar ratio of ISB / CHDM / DPC=0.700 / 0.300 / 1.010. At the same time, an aqueous solution of calcium acetate monohydrate as a catalyst was supplied to the first vertical stirring reactor in an amount of 1.5 μmol relative to 1 mol of all dihydroxy compounds. The opening of the valve of the transfer pipe provided at the bottom of the reactor was controlled so that the average residence time in the first vertical stirring reactor was 90 minutes, and the liquid level was kept constant. The reaction liquid discharged from the bottom of the reactor was then continuously supplied to the second vertical stirring reactor, the third vertical stirring reactor, and the fourth horizontal stirring reactor [twin screw double-headed blade manufactured by Hitachi Plant Technologies, Ltd.] in sequence. The first vertical stirring reactor and the second vertical stirring reactor were equipped with a reflux condenser, and the distillation of the unreacted dihydroxy compound and DPC was suppressed by adjusting the reflux ratio.

[0356] The reaction temperature, internal pressure and residence time of each reactor were as follows: 190° C., 25 kPa, 90 minutes for the first vertical stirring reactor, 195° C., 10 kPa, 45 minutes for the second vertical stirring reactor, 210° C., 3 kPa, 45 minutes for the third vertical stirring reactor, and 230° C., 0.5 kPa, 90 minutes for the fourth horizontal stirring reactor. The fourth horizontal stirring reactor was operated while finely adjusting the internal pressure so that the reduced viscosity of the obtained polycarbonate resin would be 0.61 dL / g to 0.64 dL / g.

[0357] The polycarbonate resin is continuously taken out from the fourth horizontal stirring reactor, and then the resin is directly supplied to the twin-screw extruder [TEX30α manufactured by Nippon Steel Works, Ltd.] in a molten state. The extruder has three vacuum exhaust ports to devolatilize the residual low-molecular components in the resin. The master batch pellets coated with phosphorous acid are supplied from the front of the first exhaust port, and 0.65ppm of phosphorous acid (0.2ppm in terms of phosphorus atom) is added to the polycarbonate resin. Near the second exhaust port, 2000 ppm by weight of water is added to the resin for water injection devolatilization. 500ppm of AS2112 and 1000ppm of Irganox1010 are supplied from the front of the third exhaust port. In the extruder (all 10 barrels), the barrel temperature is set to 220°C and the screw speed is set to 230rpm. The resin temperature at the extruder outlet is 262°C.

[0358] The polycarbonate resin that has passed through the extruder is then directly passed through a filter in a molten state, and after filtering out foreign matter, it is discharged from the die in a strand shape, water-cooled, and solidified, and then pelletized using a rotary cutter. The glass transition temperature of the pellets is 122° C. The obtained polycarbonate resin is referred to as PC1.

[0359] [Production Example 2]

[0360] A polycarbonate resin was obtained in the same manner as in Example 1 except that the molar ratio of ISB / CHDM / DPC was 0.700 / 0.300 / 1.012 and the mixture was continuously supplied to the first vertical stirring reactor. The glass transition temperature of the pellets was 122° C. The obtained polycarbonate resin was designated as PC2.

[0361] [Production Example 3]

[0362] The first vertical stirring reactor was continuously supplied with an aqueous solution of calcium acetate monohydrate as a catalyst at a molar ratio of ISB / CHDM / DPC = 0.700 / 0.300 / 1.000 so as to be 1.25 μmol relative to 1 mol of the total dihydroxy compound. The reaction temperature, internal pressure and residence time of each reactor were as follows: the first vertical stirring reactor: 188° C., 24.2 kPa, 90 minutes, the second vertical stirring reactor: 194° C., 19.9 kPa, 60 minutes, the third vertical stirring reactor: 214° C., 9.9 kPa, 60 minutes, the fourth horizontal stirring reactor: 225° C., 0.1 kPa, 120 minutes. In the extruder, the barrel temperatures of the first half of the four barrels were set to 240° C., the second half of the six barrels were set to 195° C., and the screw speed was set to 225 rpm. The glass transition temperature of the pellets was 122° C. The obtained polycarbonate resin was designated as PC3.

[0363] [Production Example 4]

[0364] The polymerization of polycarbonate resin was carried out using a batch polymerization device consisting of a vertical stirring reactor and a twin-screw extruder. ISB, CHDM and DPC were melted in a tank respectively, and ISB was supplied to the first vertical stirring reactor at a molar ratio of ISB / CHDM / DPC=0.700 / 0.300 / 1.000. At the same time, an aqueous solution of cesium carbonate as a catalyst was supplied to the first vertical stirring reactor in such a manner that cesium carbonate became 1.25 μmol relative to 1 mol of all dihydroxy compounds. As the first step of the reaction, the heating tank temperature was heated to 150°C, the raw materials were melted while stirring for 15 minutes, the pressure was reduced from normal pressure to 13.3 kPa in 40 minutes, and the generated phenol was taken out of the reaction container while the heating tank temperature was raised to 190°C in 40 minutes. After the entire reaction container was kept at 190°C for 15 minutes, as the second step, the heating tank temperature was raised to 240°C in 30 minutes. 10 minutes after the start of temperature rise, the pressure in the reaction container was made below 0.200 kPa in 30 minutes to distill the generated phenol. After 120 minutes, after reaching the specified stirring torque, the reaction was stopped, and the polycarbonate resin was continuously taken out from the reactor, and then the resin was directly supplied to the twin-screw extruder [TEX30α made by Nippon Steel Works, Ltd.] in a molten state. The extruder has 3 vacuum exhaust ports to devolatilize the residual low-molecular components in the resin. The master batch pellets coated with phosphorous acid were supplied from the front of the first exhaust port, and 0.65 ppm of phosphorous acid (0.2 ppm in terms of phosphorus atom) was added to the polycarbonate resin. Near the second exhaust port, 2000 ppm of water was added to the resin, and water injection devolatilization was performed. From the front of the third exhaust port, AS2112500 ppm and Irganox1010 1000 ppm were supplied. In the extruder (all 10 barrels), the barrel temperature was set to 220°C and the screw speed was set to 230 rpm. The resin temperature at the extruder outlet was 261°C.

[0365] The polycarbonate resin that has passed through the extruder is then directly passed through a filter in a molten state, and after filtering out foreign matter, it is discharged from the die in the form of strands, water-cooled, and solidified, and then pelletized using a rotary cutter. The glass transition temperature of the pellets is 122°C. The obtained polycarbonate resin is referred to as PC4.

[0366] The amounts of phenol and the compound represented by the formula (3) contained in the polycarbonate resin are summarized in Table 2 below.

[0367] [Table 2]

[0368] Table 2

[0369] PC1 PC2 PC3 PC4 Phenol content ppm 613 527 319 1094 The content of the compound represented by formula (3) ppm 392 612 1102 1342

[0370] [Example 1]

[0371] Using a quantitative feeder, 100 parts by weight of the polycarbonate resin (PC1) described in Manufacturing Example 1 and 1.5 parts by weight of UVA-1 were supplied to a twin-screw extruder with a vent (TEX30α manufactured by Nippon Steel Works, Ltd., barrel setting temperature: 240°C), foreign matter was filtered out through a filter, and the mixture was discharged from the die in the form of strands, water-cooled, and solidified, and then pelletized using a rotary cutter.

[0372] Then, the polycarbonate resin composition was extruded at 2 kg / hour in a gel counter FSA film inspection line (barrel setting temperature: 240°C, T die (width 150 mm, setting temperature: 240°C), cooling roll (setting temperature: 105°C)) manufactured by OCS Corporation into a film having a thickness of 401 μm. The results are shown in Table 3 below.

[0373] [Examples 2 to 13, Comparative Examples 1 to 5]

[0374] The same procedure as in Example 1 was carried out except that the thickness of the film, the type of the ultraviolet absorber, and the amount of the ultraviolet absorber were changed as shown in Table 3 below.

[0375] The films of Examples 1 to 13 all had particularly small values ​​for thickness accuracy and were uniform in thickness. In addition, the amount of film foreign matter per unit area was small, and they were particularly excellent films.

[0376] On the other hand, in Comparative Examples 1 to 5, the type and amount of the ultraviolet absorber used resulted in a decrease in the heat resistance of the resin composition, roll contamination due to bleeding, a deterioration in film thickness accuracy, and an increase in the amount of foreign matter.

[0377] In Comparative Examples 4 and 5, a large number of fine foreign matter were confirmed, but foreign matter of 150 μm or more, which is considered to be caused by the aggregation of the ultraviolet absorber in the entire film due to non-melting, was not observed.

[0378] [Table 3]

[0379]

[0380] [Examples 14 to 16]

[0381] As shown in Table 4 below, the same procedure as in Example 4 was carried out except that the polycarbonate resin used was changed from PC1 to any one of PC2, PC3 and PC4.

[0382] The films of Examples 14 to 16 all had particularly small values ​​for thickness accuracy and were uniform in thickness. In addition, the amount of foreign matter in the film per unit area was small, and they were particularly excellent films.

[0383] [Table 4]

[0384] Table 4

[0385] Example 4 Embodiment 14 Embodiment 15 Example 16 Use Resin PC1 PC2 PC3 PC4 UV absorber UVA-1 UVA-1 UVA-1 UVA-1 Addition amount Weight 3 3 3 3 thickness μm 25 25 25 25 Glass transition temperature ℃ 120 120 120 120 Changes in glass transition temperature ℃ -2 -2 -2 -2 380nm transmittance % 3.2 3.2 3.2 3.2 Roller contamination ○ ○- Δ Δ- Foreign matter in thin film <![CDATA[per / m 2 > 4 5 7 10 Thickness accuracy % 3 3 5 6

[0386] [Examples 17 to 19]

[0387] As shown in Table 5 below, the same procedure as in Example 6 was carried out except that the polycarbonate resin used was changed from PC1 to any one of PC2, PC3 and PC4.

[0388] The films of Examples 17 to 19 all had particularly small values ​​for thickness accuracy and were uniform in thickness. In addition, the amount of film foreign matter per unit area was small, and they were particularly excellent films.

[0389] [Table 5]

[0390] Table 5

[0391] Example 6 Embodiment 17 Embodiment 18 Embodiment 19 Use Resin PC1 PC2 PC3 PC4 UV absorber UVA-3 UVA-3 UVA-3 UVA-3 Addition amount Weight 1.1 1.1 1.1 1.1 thickness μm 25 25 25 25 Glass transition temperature ℃ 121 121 121 121 Changes in glass transition temperature ℃ -1 -1 -1 -1 380nm transmittance % 3.7 3.7 3.7 3.7 Roller contamination - ◎ ○ Δ <![CDATA[Δ - ]]> Foreign matter in thin film <![CDATA[per / m 2 > 2 3 7 9 Thickness accuracy % 1 2 5 6

[0392] [Example 20]

[0393] Using a quantitative feeder, 100 parts by weight of the polycarbonate resin (PC1) described in Manufacturing Example 1 and 1.2 parts by weight of UVA-3 were supplied to a twin-screw extruder with a vent (TEX30α manufactured by Nippon Steel Works, Ltd., barrel setting temperature: 240°C), foreign matter was filtered out through a filter, and the mixture was discharged from the die in the form of strands, water-cooled, and solidified, and then pelletized using a rotary cutter.

[0394] After that, the polycarbonate resin composition was extruded into a film having a thickness of 50 μm at a rate of 2 kg / hour in a gel counter FSA film inspection line manufactured by OCS Co., Ltd. (barrel setting temperature: 240°C, T die (width 150 mm, setting temperature: 240°C), cooling roller (setting temperature: 105°C)). An unstretched film having a length of 125 mm and a width of 50 mm was cut from the film and subjected to fixed-end uniaxial stretching at a stretching ratio of 1.8 times at a strain rate of 5 mm / min and a stretching temperature of 134°C using an intermittent biaxial stretching apparatus (manufactured by Iland Industries Co., Ltd.). The stretched transparent film was cut into a sample having a width of 4 cm and a length of 4 cm, and the in-plane phase difference R548 at a wavelength of 548 nm was measured using a phase difference measuring apparatus (manufactured by Oji Instruments Co., Ltd., product name "KOBRA WRXY2020") in a room at 23°C, and was found to be 139 nm. The results are summarized in Table 6 below.

[0395] [Table 6]

[0396] Table 6

[0397]

[0398] The polycarbonate resin film produced in Example 20 was attached as a retardation film to the screen surface of a display that displays linearly polarized light images. The display was observed through polarized sunglasses. The result was good, as it did not appear black and no rainbow pattern was observed.

[0399] The present invention is described in detail using a specific method, but it is obvious to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention. It should be noted that this application is based on Japanese patent application (Japanese Patent Application No. 2015-086969) filed on April 21, 2015, and its entirety is incorporated herein by reference.

[0400] Industrial Applicability

[0401] According to the present invention, a polycarbonate resin film can be provided which is free from problems such as reduced heat resistance of the film, turbidity of the film due to oozing substances, foreign matter in the film due to roller contamination, and poor appearance of the film such as cogwheel marks, and which is excellent in appearance quality and also has excellent uniformity in film thickness.

[0402] This is advantageous in reducing the production process loss of the polarizing plate using the polarizing plate, making the structure of the image display device thinner, and the like.

Claims

1. A polycarbonate resin film, which is a polycarbonate resin film formed from a polycarbonate resin composition, the polycarbonate resin composition comprising: 100 parts by weight of a polycarbonate resin containing a structural unit derived from a dihydroxy compound represented by the following formula (1); and, relative to 100 parts by weight of the polycarbonate resin, more than 0.45 parts by weight and less than 7 parts by weight of an ultraviolet absorber having a melting point of 135° C. or more and less than 300° C. and a 5% weight loss temperature of 245° C. or more, wherein the polycarbonate resin film has a light transmittance of 0.001% or more and less than 15% at a wavelength of 380 nm, a thickness of 5 μm to 120 μm, and the number of foreign matters in the polycarbonate resin film is 10 pieces / m 2 the following, 2. The polycarbonate resin film according to claim 1, wherein The content of the compound represented by the following formula (3) in the polycarbonate resin is 10 ppm by weight or more and 1200 ppm by weight or less, 3. The polycarbonate resin film according to claim 1 or 2, wherein The ultraviolet absorber is a triazine series, a benzotriazole series, a quinolone series, a benzoxazole series or an indole series. 4 . The polycarbonate resin film according to claim 1 , wherein the in-plane retardation at 548 nm is 100 nm to 200 nm. 5 . A polarizer protective film, comprising the polycarbonate resin film according to claim 1 .

6. A polycarbonate resin composition comprising: 100 parts by weight of a polycarbonate resin comprising a structural unit derived from a dihydroxy compound represented by the following formula (1); and an ultraviolet absorber having a melting point of 135° C. or higher and lower than 300° C. and a 5% weight loss temperature of 245° C. or higher in an amount of more than 0.45 parts by weight and less than 7 parts by weight relative to 100 parts by weight of the polycarbonate resin, wherein the content of the compound represented by the following formula (3) in the polycarbonate resin is 10 ppm by weight or more and 1,200 ppm by weight or less,